Group III nitride substrates having oxygen gradients, methods of making same, and methods of using same - Patents.com

JP2024545415A5Pending Publication Date: 2025-01-28SLT TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024532414
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-01
Filing Date
2022-11-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing methods for growing large area gallium nitride (GaN) substrates suffer from high defect levels, such as threading dislocations, warpage, stress, and distortion, which compromise the quality and reliability of optoelectronic and electronic devices, and are often limited by expensive gas phase methods like hydride vapor phase epitaxy (HVPE).

Method used

The development of free-standing GaN crystals with controlled oxygen uptake and gradients, grown using ammonothermal techniques, which reduce defect densities and improve crystal growth processes, allowing for larger substrates with reduced threading dislocations and improved structural integrity.

Benefits of technology

The solution results in GaN substrates with significantly lower defect densities, reduced warpage and stress, enabling larger, more reliable substrates suitable for various electronic and optoelectronic devices, and overcoming the limitations of current methods like HVPE.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The embodiments of the present disclosure include techniques related to techniques for processing materials to produce Group III metal nitride and gallium-based substrates. More specifically, the embodiments of the present disclosure include techniques for substrates with controlled oxygen gradients using a combination of processing techniques. By way of example only, the present disclosure can be applied to the growth of GaN, AlN, InN, InGaN, AlGaN, and AlInGaN crystals, as well as other crystals to produce bulk or patterned substrates. Such bulk or patterned substrates can be used in a variety of applications, including optoelectronic and electronic devices, lasers, light-emitting diodes, solar cells, photoelectrochemical water splitting and hydrogen generation, photodetectors, integrated circuits, and transistors.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 285,000, filed December 1, 2021, and U.S. Provisional Patent Application No. 63 / 326,448, filed April 1, 2022, both of which are incorporated herein by reference. [Technical field]

[0002] The present disclosure relates generally to techniques for processing materials to produce gallium-containing nitride substrates and the use of these substrates in optoelectronic and electronic devices. More specifically, embodiments of the present disclosure include techniques for growing large area substrates using a combination of processing techniques. [Background technology]

[0003] Gallium nitride (GaN) based optoelectronic and electronic devices are of great commercial importance. However, the quality and reliability of these devices are compromised by high defect levels, particularly threading dislocations, grain boundaries, and strain in the semiconductor layers of the devices. Threading dislocations can arise from lattice mismatch of GaN-based semiconductor layers to non-GaN substrates such as sapphire or silicon carbide. Grain boundaries can arise from coalescence fronts of epitaxially coated layers. Additional defects can arise from thermal expansion mismatch, impurities, and tilt boundaries, depending on the details of the layer growth.

[0004] Advances have been made in growing large area gallium nitride crystals, resulting in much lower defect levels than heteroepitaxial GaN layers. However, most techniques for growing large area GaN substrates involve deposition of GaN on non-GaN substrates such as sapphire or GaAs. This approach generally introduces threading dislocations into the surface of a thick boule at a rate of 10 times the thickness of the boule. 5 ~10 7 cm -2, resulting in large warpage, stress, and strain. A reduced concentration of threading dislocations is desirable for many applications. The warpage, stress, and strain can reduce yields when slicing the boule into wafers and can make the wafers more susceptible to cracking during downstream processing, which can also adversely affect device reliability and lifetime. Another consequence of the warpage, stress, and strain is that significant concentrations of stacking faults can be generated during growth in m-plane and semipolar orientations, even by near-equilibrium techniques such as ammonothermal growth. In addition, the quality of c-plane growth can be poor due to crack formation, multiple crystallographic domains, etc. The ability to produce substrates larger than 2-4 inches is currently very limited, as is the ability to produce large area GaN substrates with nonpolar or semipolar crystal orientations. Most large area substrates are produced by gas phase methods such as hydride vapor phase epitaxy (HVPE), which is relatively expensive. What is desired is a cheaper method that also achieves large area and low threading dislocation density as quickly as possible.

[0005] Ammonothermal crystal growth has many advantages over HVPE as a means of producing GaN boules. However, the performance of the ammonothermal GaN crystal growth process can be highly dependent on the size and quality of the seed crystal. Seed crystals produced by HVPE can suffer from many of the limitations mentioned above, and ammonothermally grown crystals are not widely available. Many techniques, such as lateral epitaxial overgrowth (LEO), can improve upon HVPE-derived seeds, but can still suffer from problems of distortion, cracking, and low yields.

[0006] Oxygen is a ubiquitous impurity in GaN substrates and devices, and its detrimental effects in many cases have led manufacturers to strive to minimize oxygen concentrations in their processes. However, the overall impact of oxygen on thick GaN boules and freestanding GaN wafers is not yet fully understood. Summary of the Invention [Problem to be solved by the invention]

[0007] Due to at least the above problems, there is a need for substrates having low defect densities, controlled oxygen incorporation, and formed by techniques that improve the crystal growth process, and from the above, it can be seen that techniques for improving crystal growth are highly desirable. [Means for solving the problem]

[0008] Embodiments of the present disclosure can provide a freestanding crystal comprising a Group III metal and nitrogen, the freestanding crystal including a wurtzite crystal structure, a first surface having a largest dimension greater than 40 millimeters in a first direction and a crystallographic orientation within 10 degrees of (0 0 0 1), and a second surface on an opposite side of the crystal from the first surface, the separation between the first surface and the second surface being between about 100 micrometers and about 1000 micrometers. The average oxygen concentration within the freestanding crystal at a depth of 2 to 10 micrometers from the first surface is greater than or equal to 1×10 16 cm -3 From 5×10 19 cm -3 and is between about 1.1 and about 10 times greater than the average oxygen concentration within a depth of 2 to 10 micrometers from the second surface.

[0009] The embodiments of the present disclosure may further provide a free-standing non-polar or semi-polar crystal comprising a group III metal and nitrogen, the free-standing non-polar or semi-polar crystal comprising a wurtzite crystal structure. The free-standing non-polar or semi-polar crystal comprises a first surface having a crystallographic orientation within 30 degrees of {1 0 -1 0}, a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface, and a maximum dimension in a second direction perpendicular to the first direction greater than 15 millimeters; and a second surface opposite the first surface of the crystal, the separation distance between the first surface and the second surface being between 100 micrometers and 1000 micrometers. The free-standing non-polar or semi-polar crystal may also comprise a wurtzite crystal structure having a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface, and a maximum dimension in a second direction perpendicular to the first direction greater than 15 millimeters; and a second surface opposite the first surface of the crystal, the separation distance between the first surface and the second surface being between 100 micrometers and 1000 micrometers. 3 cm -1The freestanding nonpolar or semipolar crystal also includes an average concentration of stacking faults of less than 0.1 cm at a first location along a first surface at a wavelength of 450 nanometers. -1 From 5cm -1 and at a second location along the first direction, -1 From 25cm -1 and the second location is spaced from the first location by a distance between 1 millimeter and 25 millimeters.

[0010]

[0023] Embodiments of the present disclosure may further provide a free-standing non-polar or semi-polar crystal comprising a group III metal and nitrogen, the free-standing non-polar or semi-polar crystal comprising a wurtzite crystal structure. The free-standing non-polar or semi-polar crystal comprises a first surface having a crystallographic orientation within 30 degrees of {1 0 -1 0}, a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface, and a maximum dimension in a second direction perpendicular to the first direction greater than 15 millimeters; and a second surface opposite the first surface of the crystal, the separation distance between the first surface and the second surface being between 100 micrometers and 1000 micrometers. The free-standing non-polar or semi-polar crystal comprises a wurtzite crystal structure having a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface; 3 cm -1 The freestanding non-polar or semi-polar crystal includes an average concentration of stacking faults of less than 2×10 at a first location along a first surface. 17 cm -3 From 1×10 19 cm -3 and at a second location along the first direction has a minimum value between 18 cm -3 From about 5 × 10 19 cm -3 to a maximum value between 0.01 and 0.25 mm, and the second location is spaced from the first location by a distance between 1 mm and 25 mm.

[0011]

[0023] Embodiments of the present disclosure may further provide a free-standing non-polar or semi-polar crystal comprising a group III metal and nitrogen, the free-standing non-polar or semi-polar crystal comprising a wurtzite crystal structure. The free-standing non-polar or semi-polar crystal comprises a first surface having a crystallographic orientation within 30 degrees of {1 0 -1 0}, a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface, and a maximum dimension in a second direction perpendicular to the first direction greater than 15 millimeters; and a second surface opposite the first surface of the crystal, the separation distance between the first surface and the second surface being between 100 micrometers and 1000 micrometers. The free-standing non-polar or semi-polar crystal comprises a wurtzite crystal structure having a maximum dimension in a first direction greater than 5 millimeters, the first direction comprising a projection of [0 0 0 1] on the first surface; 3 cm -1 and a difference between a maximum {20-21} lattice spacing and a minimum {20-21} lattice spacing at the first surface along a first direction is at least 2×10 -5 Å and 3×10 -4 Å or ​​less, and the separation between the local maximum {20-21} lattice constant and the local minimum {20-21} lattice constant along the first direction is between about 1 millimeter and about 25 millimeters.

[0012]

[0010] Embodiments of the present disclosure may further provide a freestanding crystal comprising a Group III metal and nitrogen, the freestanding crystal comprising a wurtzite crystal structure. The freestanding crystal comprises a first surface having a maximum dimension greater than 40 millimeters in a first direction and a crystallographic orientation within 10 degrees of (0 0 0 1); and a second surface on an opposite side of the crystal from the first surface, the spacing between the first surface and the second surface being between about 100 micrometers and about 1000 micrometers. The freestanding crystal has an average oxygen concentration within a depth of 2 to 10 micrometers from the first surface of 1×10 16 cm -3 From 5×10 19 cm -3 and is between about 1.1 and about 10 times greater than the average oxygen concentration within a depth of 2 to 10 micrometers from the second surface.

[0013] So that the above-mentioned features of the present disclosure can be understood in detail, a more particular description of the present disclosure, briefly summarized above, can be had by reference to embodiments, some of which are illustrated in the accompanying drawings, in which it is noted, however, that the accompanying drawings depict only exemplary embodiments and therefore should not be considered as limiting the scope of the present disclosure, which may admit of other equally effective embodiments. [Brief description of the drawings]

[0014] [Figure 1A] 1 is a simplified diagram illustrating the growth of a crystal on a substrate according to an embodiment of the present disclosure. [Figure 1B] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1C] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1D] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1E] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1F] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1G] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 1H] FIG. 1 is a top view of an arrangement of openings in a patterned mask layer on a seed crystal or substrate according to an embodiment of the present disclosure. [Figure 2A] FIG. 1 is a simplified schematic illustrating an epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 2B] FIG. 1 is a simplified schematic illustrating an epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 2C]FIG. 1 is a simplified schematic illustrating an epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 3A] FIG. 1 is a simplified diagram illustrating an improved epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 3B] FIG. 1 is a simplified diagram illustrating an improved epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 3C] FIG. 1 is a simplified diagram illustrating an improved epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 3D] FIG. 1 is a simplified diagram illustrating an improved epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 3E] FIG. 1 is a simplified diagram illustrating an improved epitaxial lateral overgrowth process for forming large area Group III metal nitride crystals according to an embodiment of the present disclosure. [Figure 4A] FIG. 1 is a simplified diagram illustrating a method for forming a free-standing ammonothermal Group III metal nitride boule and a free-standing ammonothermal Group III metal nitride wafer. [Figure 4B] FIG. 1 is a simplified diagram illustrating a method for forming a free-standing ammonothermal Group III metal nitride boule and a free-standing ammonothermal Group III metal nitride wafer. [Figure 5A] FIG. 1 is a simplified diagram showing threading dislocation patterns and regions on a free-standing ammonothermal Group III metal nitride boule or wafer according to an embodiment of the present disclosure. [Figure 5B] FIG. 1 is a simplified diagram showing threading dislocation patterns and regions on a free-standing ammonothermal Group III metal nitride boule or wafer according to an embodiment of the present disclosure. [Figure 5C] FIG. 1 is a simplified diagram showing threading dislocation patterns and regions on a free-standing ammonothermal Group III metal nitride boule or wafer according to an embodiment of the present disclosure. [Figure 5D]FIG. 1 is a simplified diagram showing threading dislocation patterns and regions on a free-standing ammonothermal Group III metal nitride boule or wafer according to an embodiment of the present disclosure. [Figure 5E] FIG. 1 is a simplified diagram showing threading dislocation patterns and regions on a free-standing ammonothermal Group III metal nitride boule or wafer according to an embodiment of the present disclosure. [Figure 6A] 1A-1C are cross-sectional views illustrating optical and electronic devices formed by one or more of the methods disclosed herein, according to embodiments of the present disclosure. [Figure 6B] 1A-1C are cross-sectional views illustrating optical and electronic devices formed by one or more of the methods disclosed herein, according to embodiments of the present disclosure. [Figure 7A] 1A-1C are cross-sectional views illustrating optical and electronic devices formed by one or more of the methods disclosed herein, according to embodiments of the present disclosure. [Figure 7B] 1A-1C are cross-sectional views illustrating optical and electronic devices formed by one or more of the methods disclosed herein, according to embodiments of the present disclosure. [Figure 8] FIG. 1 is a simplified diagram illustrating a method for preparing an analytical sample from a freestanding crystal according to an embodiment of the present disclosure. [Figure 9] FIG. 1 is a simplified diagram showing growth sectors and coalescence boundaries in a cross-sectional sample from a laterally grown ammonothermal laterally grown Group III metal nitride boule according to an embodiment of the present disclosure. [Figure 10] 1 is a simplified graph illustrating the dependence of aggregation distance on oxygen concentration, according to an embodiment of the present disclosure; [Figure 11] 1 is a simplified graph showing the relationship between oxygen concentration and optical absorption coefficient at a wavelength of 450 nm in cross-sections prepared from ammonothermal Group III metal nitride boules according to an embodiment of the present disclosure; [Figure 12] FIG. 1 is a simplified diagram illustrating regions of smooth and rough surface morphology on a boule formed by one or more methods disclosed herein, in accordance with an embodiment of the present disclosure. [Figure 13] 1 is a graph showing the effect of optical absorption coefficient values ​​on the percentage of surfaces exhibiting a smoother morphology, according to an embodiment of the present disclosure; [Figure 14] Graph showing the effect of oxygen concentration on the ratio of growth rates in the m-direction and -c-direction according to an embodiment of the present disclosure. [Figure 15] FIG. 1 is a simplified diagram illustrating the possible effect of oxygen incorporation on crystal growth on a strained seed crystal, according to an embodiment of the present disclosure. [Figure 16A] Graph showing the dependence of oxygen (●, left axis), hydrogen (◆, left axis), and fluorine (▲, right axis) concentrations on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. [Figure 16B] 1 is a graph showing the dependence of oxygen concentration (left axis) and optical absorption coefficient at a wavelength of 450 nm (right axis) on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. [Figure 17A] Graph showing the dependence of oxygen (●, left axis), hydrogen (◆, left axis), and fluorine (▲, right axis) concentrations on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. [Figure 17B] 1 is a graph showing the dependence of oxygen concentration (left axis) and optical absorption coefficient at a wavelength of 450 nm (right axis) on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. [Figure 18] Graph showing the dependence of oxygen (●, left axis), hydrogen (◆, left axis), and fluorine (▲, right axis) concentrations on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. [Figure 19] Graph showing the dependence of the {20-21} lattice spacing on the measurement position on a semipolar wafer surface. [Figure 20] Graph showing the dependence of oxygen (●, left axis), hydrogen (◆, left axis), and fluorine (▲, right axis) concentrations on distance from the regrowth interface in the [0 0 0 -1] direction, according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] To facilitate understanding, wherever possible, like reference numerals are used to designate like elements common to the figures. It is contemplated that elements and features of one embodiment may be beneficially incorporated in other embodiments without further recitation.

[0016] According to the present disclosure, techniques related to processing materials to produce Group III metal nitride and gallium based substrates are provided. More specifically, embodiments of the present disclosure include techniques to grow large area substrates using a combination of processing techniques. By way of example only, the present disclosure can be applied to the growth of GaN, AlN, InN, InGaN, AlGaN, and AlInGaN crystals, as well as other crystals to produce bulk or patterned substrates. Such bulk or patterned substrates can be used in a variety of applications, including optoelectronic devices, laser diodes, light emitting diodes, photodiodes, solar cells, photoelectrochemical water splitting and hydrogen generation, photodetectors, integrated circuits, and transistors.

[0017] Oxygen is a ubiquitous impurity in nitrides, including GaN, AlN, InN, and their alloys, and is typically present in higher concentrations in ammonothermal GaN compared to GaN grown by other methods, such as HVPE. Oxygen exists as a substitutional impurity for nitrogen and acts as an n-type dopant in GaN. However, oxygen also causes an increase in the lattice constant [C. Van de Walle, Phys. Rev. B68, 165209 (2003)], which means that oxygen gradients within GaN crystals can cause stress and cracks, especially in GaN crystals with thicknesses greater than 0.1 mm, 0.3 mm, 1 mm, or 10 mm. In addition, in ammonothermal GaN, oxygen incorporation is typically accompanied by the formation of Ga vacancies decorated with H and / or O [e.g., W. Jiang et al., U.S. Pat. No. 9,543,392], which can cause light absorption below the bandgap, darkening of the crystal and wafer, and further increase in the lattice constant.Ga vacancy complexes with oxygen and / or hydrogen have been studied by many researchers [CG Van de Walle, Phys. Rev. B56, R10020 (1997); K. Saarinen, et al., Phys. Rev. B64, 233301 (2001); F. Tuomisto, et al., Appl. Phys. Lett. 86, 031915 (2005); S. Hautakangas, et al., Phys. Rev. B73, 193301 (2006); F. Tuomisto, et al., Phys. Stat. Solidi (b) 243, 1436 (2006); NT Son, et al., Phys. Rev. B80, 153202 (2009); F. Tuomisto, et al., J. Crystal Growth 312, 2620 (2010); F. Tuomisto, et al., J. Crystal Growth 403, 114 (2014); S. Suihkonen, et al., Appl.Phys.Lett. 108, 202105 (2016); CE Dreyer, et al., Appl. Phys.Lett.108, 141101 (2016); A. Uedono, et al., J. Crystal Growth 448, 117 (2016); K. Jiang, et al., Appl. Phys. Express 10, 075506 (2017); K. Iso, et al., Appl. Phys. Express 12, 125502 (2019); MA Reschikov, J. Appl. Phys.129, 095703 (2021)], but the determination of their specific impact on the lattice constant of GaN is unknown.

[0018] Sintonen et al. [J. Crystal Growth 456, 51 (2016)] characterized the distribution of oxygen and other impurities in the cross-section of ammonobase-grown crystals and found that the oxygen level was nearly constant across the thickness of the crystal, which grew successively over several growth runs, with some upward and some downward gradients, and further fluctuations in the immediate vicinity of the regrowth interface that generated distortion.

[0019] Because of the deleterious effects of oxygen, including distortion and optical absorption, many groups have sought to minimize the oxygen concentration in the raw materials, in the crystal growth environment, and in the nitride crystal. For example, D'Evelyn et al. [U.S. Pat. No. 7,078,731] reported that by keeping the total oxygen content in the raw materials and the capsule housing the raw materials below 15 ppm or 1.5 ppm, respectively, by weight of the final crystal, the oxygen concentration in the grown crystal was reduced to 3×10 18 cm -3 Or 3 x 10 17 cm -3 D'Evelyn et al. [U.S. Pat. No. 8,461,071] taught the formation of polycrystalline GaN incorporating a getter such that the oxygen content, present as Ga2O3 or as a substitutional impurity in the polycrystalline gallium nitride, is close to or less than about 0.1 ppm.

[0020] Surprisingly, the inventors have discovered that oxygen impurities and artificial oxygen gradients within certain ranges in GaN crystals can provide many benefits to ammonothermal GaN crystal growth in addition to n-type doping. It is well known that oxygen incorporation in ammonothermal GaN varies depending on the crystallographic branch (e.g., Jiang et al., U.S. Pat. No. 9,453,392; Sintonen, et al., J. Crystal Growth 456, 43 (2016)), and therefore it may be beneficial to confine the crystal growth process primarily to one crystallographic branch (e.g., as described in D'Evelyn's U.S. Pat. No. 8,979,999). In certain embodiments, the crystal growth process is selected to be primarily in the [0 0 0 -1] or -c direction.

[0021] 1A is a schematic cross-sectional view of a bulk GaN crystal 117 grown on a substrate 101 with predominantly a single crystal orientation. In a particular embodiment, the substrate 101 consists of or includes a substrate material that is a single crystal Group III metal nitride, a gallium-containing nitride, or gallium nitride. The substrate 101 may be grown by HVPE, ammonothermally, or by a flux method. One or both of the large area surfaces of the substrate 101 may be polished and / or chemically mechanically polished. The large area surface 102 of the substrate 101 may have a crystallographic orientation within 10 degrees, 5 degrees, 2 degrees, 1 degree, or 0.5 degrees of the (0001)+c-plane, the (000-1)-c-plane, the {10-10}m-plane, {11-2±2}, {60-6±1}, {50-5±1}, {40-4±1}, {30-3±1}, {50-5±2}, {70-7±3}, {20-2±1}, {30-3±2}, {40-4±3}, {50-5±4}, {10-1±1}, {10-1±2}, {10-1±3}, {21-3±1}, or {30-3±4}. The large area surface 102 can have a (hkil) semi-polar orientation, where i=-(h+k) and l, and at least one of h and k is non-zero. The large area surface 102 can have a maximum lateral dimension between about 5 millimeters and about 600 millimeters and a minimum lateral dimension between about 1 millimeter and about 600 millimeters, and the substrate 101 can have a thickness between about 10 micrometers and about 10 millimeters, or between about 100 micrometers and about 2 millimeters.

[0022] The substrate 101 is approximately 10 7 cm -2 Less than, about 10 6 cm -2 Less than, about 10 5 cm -2 Less than, about 10 4 cm -2 Less than, about 10 3 cm -2 Less than or about 10 2 cm -2 The substrate 101 may have a surface threading dislocation density of less than about 10 4 cm -1 Less than, about 10 3cm -1 Less than, about 10 2 cm -1 Less than 10cm -1 Less than or about 1 cm -1 The substrate 101 may have a stacking fault concentration of less than about 500 arc seconds, less than about 300 arc seconds, less than about 200 arc seconds, less than about 100 arc seconds, less than about 50 arc seconds, less than about 35 arc seconds, less than about 25 arc seconds, or less than about 15 arc seconds. The substrate 101 may have a crystal radius of curvature of greater than 0.1 meters, greater than 1 meter, greater than 10 meters, greater than 100 meters, or greater than 1000 meters in at least one, at least two, or three independent or orthogonal directions.

[0023] The substrate 101 may include regions having a relatively high concentration of threading dislocations separated by regions having a relatively low concentration of threading dislocations. The concentration of threading dislocations in the relatively high concentration regions may be about 10 5 cm -2 Super, about 10 6 cm -2 Super, about 10 7 cm -2 More than or about 10 8 cm -2 The concentration of threading dislocations in the relatively low concentration region can be about 10 6 cm -2 Less than, about 10 5 cm -2 Less than or about 10 4 cm -2The thickness of the substrate 101 may be less than about 10 micrometers. The substrate 101 may include regions having relatively high electrical conductivity separated by regions having relatively low electrical conductivity. The substrate 101 may have a thickness of between about 10 micrometers and about 100 millimeters, or between about 0.1 millimeters and about 10 millimeters. The substrate 101 may have a maximum dimension (including diameter) of at least about 5 millimeters, at least about 10 millimeters, at least about 25 millimeters, at least about 50 millimeters, at least about 75 millimeters, at least about 100 millimeters, at least about 150 millimeters, at least about 200 millimeters, at least about 300 millimeters, at least about 400 millimeters, or at least about 600 millimeters.

[0024] The large area surface 102 (FIG. 1A) can have a crystallographic orientation within about 5 degrees of the (000-1) N-plane, c-plane orientation, and can have an x-ray diffraction ω-scan rocking curve full width at half maximum (FWHM) of less than about 200 arc seconds, less than about 100 arc seconds, less than about 50 arc seconds, or less than about 30 arc seconds for the (002) and / or (102) reflections, and can have an x-ray diffraction ω-scan rocking curve full width at half maximum (FWHM) of less than about 10 7 cm -2 Less than, about 10 6 cm -2 Less than or about 10 5 cm -2 In some embodiments, the threading dislocations in the large area surface 102 are substantially uniformly distributed. In other embodiments, the threading dislocations in the large area surface 102 are non-uniformly arranged as a one-dimensional array of rows of relatively high and relatively low concentration regions within a matrix of low dislocation density regions or as a two-dimensional array of high dislocation density regions. The crystallographic orientation of the large area surface 102 may be substantially constant, i.e., may vary by less than about 5 degrees, less than about 2 degrees, less than about 1 degree, less than about 0.5 degrees, less than about 0.2 degrees, less than about 0.1 degrees, or less than about 0.05 degrees.

[0025] In certain embodiments, the large area surface 102 is etched, for example to remove surface damage or to improve adhesion of a mask layer, hi certain embodiments, the large area surface 102 is etched by one or more of chemical etching, electrochemical etching, photoelectrochemical etching, reactive ion etching, chemically assisted ion beam etching, or other forms of wet or dry etching.

[0026] In a particular embodiment, a patterned mask layer is provided on the large area surface 102 prior to growing ammonothermal GaN crystals 117 on the substrate 101. FIGS. 1B-1H are top views showing the arrangement of growth centers 120 in a patterned mask layer 111 on the substrate 101. In a particular embodiment, the growth centers 120 include or consist of a set of exposed areas of the substrate 101, e.g., openings in the patterned mask layer (not shown in FIGS. 1B-1H, but see FIG. 2A), that function as growth centers. As shown in FIG. 2A, the patterned mask layer 111 may include one, two, or more of an adhesion layer 105, a diffusion barrier layer 107, and an inert layer 109, and the growth centers 120 may include or consist of openings 112 in the patterned mask layer 111. The adhesion layer 105 may be a TiN, ... y , TiSi2, Ta, TaN y , Al, Ge, Al x Ge y , Cu, Si, Cr, V, Ni, W, TiW x , TiW x N y The diffusion barrier layer 107 may include one or more of TiN, TiN y , TiSi2, W, TiW x , TiN y , W.N. y ,TaN y , TiW x N y , TiW x S z N y, TiC, TiCN, Pd, Rh, Cr, etc., and have a thickness between about 1 nanometer and about 10 micrometers. The passivation layer 109 may include one or more of Au, Ag, Pt, Pd, Rh, Ru, Ir, Ni, Cr, V, Ti, or Ta, and may have a thickness between about 10 nanometers and about 100 micrometers. The one or more patterned mask layers 111 may be deposited by sputter deposition, thermal evaporation, e-beam evaporation, electroplating, electroless plating, a combination or sequence of these techniques, etc.

[0027] The exposed regions or openings 112 may be formed by one or more of negative photoresist lift-off, shadow masking, positive photoresist reactive ion etching, wet chemical etching, ion milling, and nanoimprint lithography, laser cutting, etc. In one particular embodiment, a trench is provided beneath the exposed growth centers 120.

[0028] In certain embodiments, the exposed growth center regions (or also referred to herein as growth centers 120) are arranged in a one-dimensional (1D) array in the y direction, such as a single row of exposed growth centers 120, as shown in Figure 1E. In certain embodiments, the exposed growth centers 120 are arranged in a two-dimensional (2D) array in the x and y directions, as shown in Figures 1B-1D and 1F-1H. The openings in the patterned mask layer 111, and thus the exposed growth centers 120, may be circular, square, rectangular, triangular, hexagonal, etc., and may have an opening dimension or diameter W of between about 1 micrometer and about 5 millimeters, or between about 10 micrometers and about 500 micrometers, as shown in Figures 1B-1H. The exposed growth centers 120 can be arranged in a 2D hexagonal or square array with a pitch dimension L between about 5 micrometers and about 20 millimeters, between about 200 micrometers and about 15 millimeters, or between about 500 micrometers and about 10 millimeters, or between about 0.8 millimeters and about 5 millimeters, as shown in Figures 1B and 1C. The exposed growth centers 120 can be arranged in a 2D array, where the pitch dimension L1 in the y direction and the pitch dimension L2 in the x direction can be different from each other, as shown in Figures 1D and 1F-1H. The exposed growth centers 120 can be arranged in a rectangular, parallelogram, hexagonal, or trapezoidal array (not shown), where the pitch dimension L1 in the y direction and the pitch dimension L2 in the x direction can be different from each other, as shown in Figures 1D and 1F-1H. The array of exposed growth centers 120 can be linear or irregular in shape. The exposed growth centers 120 in the patterned mask layer(s) 111 can be aligned with the structure of the substrate 101. For example, in one particular embodiment, the large-area surface 102 is hexagonal in shape in the XY plane ( FIG. 1 ), e.g., with a (0001) or (000-1) crystal orientation, and the openings in the patterned mask layer(s) 111 comprise a 2D hexagonal array such that the separation between nearest adjacent openings is parallel to the <11-20> or <10-10> direction of the large-area surface 102.In a particular embodiment, the large area surface 102 of the substrate is non-polar or semi-polar, and the exposed growth centers 120 comprise a 2D square or rectangular array such that the separation between nearest adjacent openings is parallel to the projection of two of the c-axis, m-axis, and a-axis on the large area surface 102 of the substrate 101. In a particular embodiment, the pattern of exposed growth centers 120 is oriented obliquely with respect to the structure of the substrate 101, e.g., the exposed growth centers 120 are rotated between about 1 degree and about 44 degrees with respect to a high symmetry axis of the substrate, such as the projection of the c-axis, m-axis, or a-axis on the large area surface 102 of the substrate 101, which has a hexagonal crystal structure, such as a wurtzite crystal structure. In a particular embodiment, the exposed growth centers 120 are substantially linear rather than substantially circular. In a particular embodiment, the exposed growth centers 120 are slits having a width W and a period L that extend the entire length of the substrate 101, as shown in FIG. 1E. In certain embodiments, the exposed growth centers 120 are slits having a width W1 in the y direction and a predetermined length W2 in the x direction that is less than the length of the substrate 101, and may be arranged in a 2D linear array with period L1 in the y direction and period L2 in the x direction, as shown in Figures 1F-1H. In some embodiments, adjacent rows of exposed growth centers 120 (e.g., slits) may be offset from each other in the x direction rather than being positioned directly adjacent, as shown in Figure 1G. In certain embodiments, adjacent rows of exposed growth centers 120 (e.g., slits) may be offset from each other in the longitudinal y direction. In certain embodiments, the exposed growth centers 120 include slits that extend in two or more different directions, such as the x direction and the y direction, as shown in Figure 1H. In certain embodiments, the exposed growth centers 120 (e.g., slits) may be arranged to reflect the hexagonal symmetry of the substrate. In certain embodiments, the exposed growth centers 120 (e.g., slits) may extend to the edges of the substrate 101.

[0029] In a particular embodiment, the back side of the substrate 101 is masked with a pattern similar to one of the above patterns, using a material similar to the patterned mask layer 111. In a particular embodiment, the back side of the substrate 101 is masked with a material similar to the patterned mask layer 111, and there are no openings or growth centers on the back side, so that subsequent crystal growth occurs only on the front side and possibly on the edges of the substrate 101. In a particular embodiment, the back side of the substrate 101 is not masked, but is covered, for example using a metal foil or a seed mounting fixture, so that subsequent crystal growth occurs only on the front side and possibly on the edges of the substrate 101. In a particular embodiment, the back side of the substrate 101 is left open and is then exposed to a crystal growth environment, so that crystal growth occurs on both the front and back side of the substrate 101, as well as possibly on the edges.

[0030] Additional details regarding the preparation of substrates with patterned exposed areas are described in U.S. Pat. No. 9,589,792 and U.S. Patent Application Publication No. 2021 / 0249252.

[0031] The substrate 101 may be maskless (FIG. 1A), patterned (FIG. 2A), or patterned with a trench 115 (FIG. 3A) and then used as a substrate for bulk crystal growth, including, for example, ammonothermal, HVPE, or flux growth. In the following description, the grown GaN layer is referred to as an ammonothermal layer, but other bulk growth methods such as HVPE or flux growth may be used instead. In certain embodiments involving ammonothermal bulk growth, the substrate 101 to be patterned may then be suspended on a seed rack and placed in a sealable container such as a capsule, an autoclave, or a liner within an autoclave. In certain embodiments, one or more pairs of patterned substrates are suspended back to back, with the patterned large area surfaces facing outward. A source of Group III metal, such as a polycrystalline Group III metal nitride, at least one mineralizer composition, and ammonia (or other nitrogen-containing solvent) are then added to a sealable container (e.g., a capsule or autoclave), and the sealable container is sealed. The mineralizer composition may include an alkali metal, such as Li, Na, K, Rb, or Cs, an alkaline earth metal, such as Mg, Ca, Sr, or Ba, or an alkali or alkaline earth hydride, amide, imide, amide-imide, nitride, or azide. The mineralizer may include an ammonium halide, such as NHF, NH4Cl, NH4Br, or NHI, a gallium halide, such as GaF3, GaCl3, GaBr3, GaI3, or any compound that can be formed by the reaction of one or more of F, Cl, Br, I, HF, HCl, HBr, HI, Ga, GaN, and NH3. The mineralizers may include other alkali, alkaline earth, or ammonium salts, other halides, urea, sulfur or sulfide salts, or phosphorus or phosphorus-containing salts. The sealable container (e.g., capsule) can then be placed in a high pressure apparatus, such as an internally heated high pressure apparatus or an autoclave, and the high pressure apparatus can be sealed. The sealable container containing the substrate 101 to be patterned is then heated to a temperature of greater than about 400° C. and subjected to a pressure of greater than about 50 megapascals to perform ammonothermal crystal growth.In a particular embodiment, the substrate is exposed to an etch-back process, for example, by applying a reverse or reduced temperature gradient, i.e., a temperature gradient that is opposite in sign and / or reduced in magnitude to the temperature gradient used for crystal growth. For example, the reverse temperature gradient may have a value between about 1° C. and about 50° C. and may be held for about 1 minute to about 24 hours. The reduced temperature gradient may have a range of 0° C. to 5° C. and may be held for about 1 minute to about 24 hours. In a particular embodiment, the etch-back process removes a thickness of between about 1 micrometer and about 50 micrometers from one or more surfaces of the substrate 101 before the start of growth.

[0032] FIG. 1A illustrates the growth of bulk crystals on an unmasked substrate over a large area surface 102. FIGS. 2A-2C illustrate the growth of bulk crystals by a lateral epitaxial overgrowth (LEO) process without a trench under the mask opening. During the bulk crystal growth process, a group III metal nitride layer 213 grows through the opening 112 in the patterned mask layer 111, grows outward through the opening, and grows laterally on the patterned mask layer 111 and coalesces, as shown in FIG. 2C. After coalescence, the group III metal nitride layer 213 includes a window region 215 that grew perpendicular to the opening in the patterned mask layer 111, a wing region 217 that grew laterally on the patterned mask layer 111, and a coalescence front 219 that forms at the boundary between the wings growing from adjacent openings in the patterned mask layer 111. The threading dislocations 214 may be present in the window region 215 , originating from threading dislocations that were present on the surface of the substrate 101 .

[0033] 3A-3C illustrate a bulk Group III nitride sidewall LEO process. FIG. 3A illustrates a substrate including a patterned and masked trench 115 formed, for example, by wet etching and / or laser patterning. In a sidewall LEO process, Group III metal nitride material 221 grows on the sides and bottom of the patterned and masked trench 115, as shown in FIG. 3B. As the Group III metal nitride material 221 on the sidewall of the trench 115 grows inward, it becomes increasingly difficult for the Group III nitride source material to reach the bottom of the trench, whether the source material includes an ammonothermal complex of a Group III metal (for ammonothermal growth), a Group III metal halide (for HVPE), or a Group III metal alloy or inorganic complex (for flux growth). Eventually, the Group III metal nitride material 221 pinches off the lower region of the trench, forming a void 225, as shown in FIG. 3C. It has been found that the concentration of threading dislocations in the laterally grown group-III metal nitride material 221 is lower than that in the substrate 101. Many of the threading dislocations 223 originating from the substrate 101 terminate at the surface of the voids 225. Concomitantly, the group-III metal nitride layer 213 grows upward through the openings 112 (or windows) in the patterned mask layer 111. However, because the laterally grown group-III metal nitride material 221 has a lower concentration of threading dislocations than the substrate 101, and many of the dislocations originating from the substrate 101 terminate at the surface of the voids 225, the dislocation density of the vertically grown group-III metal nitride layer 213 is significantly reduced compared to the conventional LEO process, as described above in connection with FIGS. 2A-2C.

[0034] 3D-3E show a continuation of the sidewall LEO growth process. Similar to the conventional LEO process (FIGS. 2A-2C), the group III metal nitride layer 213 grows within the opening 112 in the patterned mask layer 111, grows outward through the opening, and then grows laterally on the patterned mask layer 111 and coalesces, as shown in FIG. 3D. After coalescence, the group III metal nitride layer 213 includes a window region 215 (FIG. 3E) that grew perpendicular to the opening 112 in the patterned mask layer 111, a wing region 217 that grew laterally on the patterned mask layer 111, and a coalescence front 219 that forms at the boundary between the wings growing from adjacent openings in the patterned mask layer 111, as shown in FIG. 3E. The laterally grown Group III metal nitride material 221 has a lower concentration of threading dislocations than the substrate 101, and since many of the threading dislocations originating from the substrate 101 terminate in voids 225, the concentration of threading dislocations in the window region 215 is significantly lower than in conventional LEO.

[0035] The ammonothermal Group III metal nitride layer 213 may have a thickness, measured in the Z direction shown in FIG. 3E, between about 10 micrometers and about 100 millimeters, or between about 100 micrometers and about 20 millimeters.

[0036] In one particular embodiment, the ammonothermal Group III metal nitride layer 213 is subjected to one or more processes, such as at least one of sawing, lapping, grinding, polishing, chemical-mechanical polishing, or etching.

[0037] In a particular embodiment, the concentration of extended defects such as threading dislocations and stacking faults in the ammonothermal Group III metal nitride layer 213 can be quantified by defect-selective etching. The defect-selective etching can be performed using a solution including one or more of H3PO4, H3PO4 prepared by extended heat treatment to form polyphosphoric acid, and H2SO4, or a molten flux including one or more of NaOH and KOH. The defect-selective etching can be performed at a temperature between about 100° C. and about 500° C. for a period of about 5 minutes to about 5 hours, with the process temperature and time selected to result in the formation of etch pits having a diameter between about 1 micrometer and about 25 micrometers, followed by removal of the ammonothermal Group III metal nitride layer, crystal, or wafer from the etchant solution.

[0038] The concentration of threading dislocations at the surface of the window region 215 is about 10 to about 10 times higher than the concentration in the underlying substrate 101. 4 The concentration of threading dislocations at the surface of the window region 215 can be approximately 10 8 cm -2 Less than, about 10 7 cm -2 Less than, about 10 6 cm -2 Less than, about 10 5 cm -2 Less than or about 10 4 cm -2 The concentration of threading dislocations at the surface of the wing regions 217 can be about one to about three orders of magnitude lower than the concentration of threading dislocations at the surface of the window regions 215, and can be about 10 5 cm -2 Less than, about 10 4 cm -2 Less than, about 10 3 cm -2 Less than, about 10 2 cm -2 Less than or about 10cm -2 Some stacking faults may be less than about 1 cm -1 About 10 4 cm -1The concentration of stacking faults at the surface of the window region 215 may be about one to about three orders of magnitude lower than at the surface of the wing region 217, and may be about 10 2 cm -1 Less than 10cm -1 Less than 1cm -1 Less than or about 0.1 cm -1 Threading dislocations, e.g., edge dislocations, may be, for example, less than about 1×10 5 cm -1 Less than 3×10 4 cm -1 Less than 1×10 4 cm -1 Less than 3×10 3 cm -1 Less than 1×10 3 cm -1 Less than 3×10 2 cm -1 Less than or 1×10 2 cm -1 Dislocations may be present at the coalescence front 219 at a linear density of less than 5 cm. -1 Super, 10cm -1 Super, 20cm -1 Super, 50cm -1 Super, 100cm -1 Super, 200cm -1 Over 500cm -1 It could be super.

[0039] In certain embodiments, the masking and bulk III-nitride crystal growth process is repeated one, two, three, or more times. In some embodiments, these operations are performed while the first bulk III-nitride metal layer remains bonded to the substrate 101. In other embodiments, the substrate 101 is removed, for example, by sawing, lapping, grinding, and / or etching, prior to the subsequent masking and bulk crystal growth operations.

[0040] 4A and 4B are simplified diagrams illustrating a method for forming a free-standing group-III metal nitride boule and a free-standing group-III metal nitride wafer. In one particular embodiment, the substrate 101 is removed from the ammonothermal group-III metal nitride layer 213 (FIG. 3E), or the last such layer deposited, to form a free-standing ammonothermal group-III metal nitride boule 413. Removal of the substrate 101 may be accomplished by one or more of cutting, grinding, lapping, polishing, laser lift-off, self-isolation, and etching to form a processed free-standing laterally grown group-III metal nitride boule 413. The processed free-standing laterally grown group-III metal nitride boule 413 may include a similar or substantially identical composition to the ammonothermal group-III metal nitride layer, and the etching may be performed under conditions in which the etch rate of the backside of the substrate 101 is much faster than the etch rate of the frontside of the ammonothermal group-III metal nitride layer. In certain embodiments, a portion of the ammonothermal Group III metal nitride layer 213, or the last such layer deposited, may be protected from attack by the etchant by depositing a mask layer, encasing a portion of the layer in Teflon, clamping a portion of the layer against Teflon, painting with Teflon paint, etc. In certain embodiments, the substrate 101 comprises single crystal gallium nitride, the large area surface 102 of the substrate 101 has a crystallographic orientation within about 5 degrees of the (0001) crystallographic orientation, and the substrate 101 is preferentially etched by heating at a temperature between about 150° C. and about 500° C. for about 30 minutes to about 5 hours in a solution comprising one or more of H3PO4, H3PO4 prepared by extended heat treatment to form polyphosphoric acid, and H2SO4, or by heating in a molten flux comprising one or more of NaOH and KOH. Surprisingly, the patterned mask layer(s) 111 can facilitate preferential removal of the substrate 101 by acting as an etch stop.The processed freestanding ammonothermal group III metal nitride boule 413 may include one or more window regions 415 formed over exposed growth centers 120, such as openings 112 in patterned mask layer(s) 111 on the substrate 101. The processed freestanding laterally grown group III metal nitride boule 413 may also include one or more wing regions 417 formed over non-opening regions of the patterned mask layer(s) 111, and a pattern of locally approximately linear arrays 419 of threading dislocations, as shown in FIG. 4A. One or more of the front surface 421 and back surface 423 of the freestanding ammonothermal group III metal nitride boule 413 may be lapped, polished, etched, and chemically mechanically polished. As also described above, the pattern of the locally nearly linear array 419 may include a coalescence front region that includes a "sharp boundary" having a width of less than about 25 micrometers or less than about 10 micrometers disposed between adjacent wing regions 417, or an "extended boundary" having a width of between about 25 micrometers and about 1000 micrometers, or between about 30 micrometers and about 250 micrometers disposed between adjacent wing regions 417, depending on the growth conditions.

[0041] In a particular embodiment, the edges of the freestanding ammonothermal Group III metal nitride boule 413 are ground to form a cylindrical shaped ammonothermal Group III metal nitride boule. In a particular embodiment, one or more flat surfaces are ground into the sides of the freestanding ammonothermal Group III metal nitride boule 413. In a particular embodiment, the freestanding ammonothermal Group III metal nitride boule 413 is sliced ​​into one or more freestanding ammonothermal Group III metal nitride wafers 431 as shown in FIG. 4B. Slicing can be performed by multi-wire saw cutting, multi-wire slurry saw cutting, slicing, ID saw cutting, OD saw cutting, cleaving, ion implantation followed by peeling, spalling, laser cutting, and the like. One or more large area surfaces of the freestanding ammonothermal Group III metal nitride wafer 431 can be lapped, polished, etched, electrochemically polished, photoelectrochemically polished, reactive ion etched, and / or chemically mechanically polished according to methods known in the art. In certain embodiments, the chamfer, bevel, or rounded edge is ground into the edge of the freestanding ammonothermal Group III metal nitride wafer 431. The freestanding ammonothermal Group III metal nitride wafer can have a diameter of at least about 5 millimeters, at least about 10 millimeters, at least about 25 millimeters, at least about 50 millimeters, at least about 75 millimeters, at least about 100 millimeters, at least about 150 millimeters, at least about 200 millimeters, at least about 300 millimeters, at least about 400 millimeters, or at least about 600 millimeters, and can have a thickness of between about 50 micrometers and about 10 millimeters, or between about 150 micrometers and about 1 millimeter. One or more large area surfaces of the freestanding ammonothermal Group III metal nitride wafer 431 can be used as a substrate for growth of Group III metal nitrides by, among other techniques, chemical vapor deposition, metalorganic chemical vapor deposition, hydride vapor phase epitaxy, molecular beam epitaxy, flux growth, solution growth, ammonothermal growth, and the like.

[0042] 5A-5E are simplified diagrams illustrating threading dislocation patterns formed in a freestanding group-III metal nitride boule 413 or wafer 431. The large area surface (e.g., front surface 421 or back surface 423) of the freestanding ammonothermal group-III metal nitride boule 413 or wafer 431 can be characterized by a pattern of locally approximately linear arrays 419 of threading dislocations propagated from a coalescence front 219 formed during the epitaxial lateral overgrowth process, as discussed above in connection with FIGS. 3A-3E. The pattern of the locally approximately linear arrays of threading dislocations can be 2D hexagonal, square, rectangular, trapezoidal, triangular, 1D linear, or irregular patterns formed at least in part due to the pattern of exposed growth centers 120 (FIGS. 1F-1L) used during the process to form the freestanding laterally grown group-III metal nitride boule 413. One or more window regions 415 are formed over exposed growth centers 120 (FIGS. 1F-1L), and one or more wing regions 417 are formed in portions not overlying exposed growth centers 120, i.e., portions formed by lateral growth. As discussed above, the formed coalescence front 219 or pattern of locally approximately linear arrays 419 may include coalescence front regions having lateral widths (i.e., measured parallel to the surface of the page containing FIGS. 5A-5E) that may vary depending on the growth conditions.

[0043] More complex patterns are also possible and may be advantageous in that they are, for example, more resistant to cracking or cleaving. The pattern 502 may be elongated in one direction compared to another orthogonal direction, for example, due to the freestanding laterally grown group III metal nitride boule 413 being sliced ​​at an oblique angle relative to the large area surface of the freestanding ammonothermal group III metal nitride boule 413. The locally approximately linear array of threading dislocations pattern 502 may be characterized by a linear array of threading dislocations having a pitch dimension L between about 5 micrometers and about 20 millimeters, or between about 200 micrometers and about 5 millimeters (FIG. 5D). The locally approximately linear array of threading dislocations pattern 502 may be characterized by a pitch dimension L between about 5 micrometers and about 20 millimeters, or between about 200 micrometers and about 5 millimeters, or between about 500 micrometers and about 2 millimeters (FIGS. 5A, 5B), or pitch dimensions L1 and L2 in two orthogonal directions (FIGS. 5C and 5E). In certain embodiments, the pattern 502 of locally approximately linear arrays of threading dislocations is approximately aligned with the underlying crystal structure of the Group III metal nitride, e.g., the locally approximately linear arrays are located on one or more of <10-10>, <11-20>, or [000±1], or within about 5 degrees, within about 2 degrees, or within about 1 degree of their projection in the plane of the surface of the freestanding ammonothermal Group III metal nitride boule 413 or Group III metal nitride wafer 431. The linear concentration of threading dislocations in the pattern is approximately 1×10 5 cm -1 Less than 3×10 4 cm -1 Less than 1×10 4 cm -1 Less than 3×10 3 cm -1 Less than 1×10 3 cm -1 Less than 3×10 2 cm -1 Less than or about 1 x 10 2 cm -1 The linear concentration of threading dislocations in the pattern 502 may be less than 5 cm -1 Super, 10cm-1 Super, 20cm -1 Super, 50cm -1 Super, 100cm -1 Super, 200cm -1 Over 500cm -1 It could be super.

[0044] 5A-5E, the large area surface of a freestanding ammonothermal Group III metal nitride boule or wafer (e.g., front surface 421 or back surface 423 of FIGS. 4A-4B) can be characterized by an array of wing regions 417 and an array of window regions 415. Each wing region 417 can be positioned between adjacent locally approximately linear arrays 419 of threading dislocations. Each window region 415 can be disposed within a single wing region 417 or can be positioned between two adjacent wing regions 417, and can have a minimum dimension between 10 micrometers and 500 micrometers, and can have a minimum dimension between 10 micrometers and 500 micrometers. 3 cm -2 From 10 8 cm -2 This can be characterized by a threading dislocation concentration between 10 3 cm -1 In some embodiments, the boundary between the window region and the wing region has a thickness of less than about 5 cm. -1 From 10 5 cm -1 The dislocations may be provided at a linear density between .

[0045] The array may be elongated in one direction compared to another orthogonal direction, for example, due to the boule being sliced ​​at an oblique angle relative to the large area surface of the freestanding ammonothermal Group III metal nitride boule. The pattern of the locally approximately linear array of threading dislocations 419 may be characterized by a pitch dimension L between about 5 micrometers and about 20 millimeters, or between about 200 micrometers and about 5 millimeters, or pitch dimensions L1 and L2 in two orthogonal directions. In certain embodiments, the pattern of the locally approximately linear array of threading dislocations 419 is approximately aligned with the underlying crystal structure of the Group III metal nitride, for example, the locally approximately linear array is located within one or more of <10-10>, <11-20>, or [000±1], or within about 5 degrees, within about 2 degrees, or within about 1 degree of their projection in the plane of the surface of the freestanding ammonothermal Group III nitride boule or wafer. The linear concentration of threading dislocations in the pattern is about 1×10 5 cm -1 Less than 3×10 4 cm -1 Less than 1×10 4 cm -1 Less than 3×10 3 cm -1 Less than 1×10 3 cm -1 Less than 3×10 2 cm -1 Less than or about 1 x 10 2 cm -1 The linear concentration of threading dislocations in the pattern can be less than 5 cm -1 Super, 10cm -1 Super, 20cm -1 Super, 50cm -1 Super, 100cm -1 Super, 200cm -1 Over 500cm -1 It could be super.

[0046] The concentration of threading dislocations in the wing regions 417 between the locally nearly linear arrays of threading dislocations is about 10 5 cm -2 Less than, about 10 4 cm -2 Less than, about 103 cm -2 Less than, about 10 2 cm -1 Less than or about 10cm -2 The concentration of threading dislocations at the surface of the window region 415 can be less than about 10 8 cm -2 Less than, about 10 7 cm -2 Less than, about 10 6 cm -2 Less than, about 10 5 cm -2 Less than or about 10 4 cm -2 The concentration of threading dislocations at the surface of the window region may be at least 2 times, at least 3 times, at least 10 times, at least 30 times, or at least 100 times higher than the concentration of threading dislocations at the surface of the wing region. The concentration of threading dislocations at the surface of the window region may be at least 10 times, at least 30 times, or at least 100 times higher than the concentration of threading dislocations at the surface of the wing region. 4 4. The boundary between the window region 415 and the wing region 417 may be less than about 5 cm, 3000 times, 1000 times, 300 times, 100 times, or 30 times higher. In some embodiments, the boundary between the window region 415 and the wing region 417 may be less than about 5 cm, for example. -1 From 10 5 cm -1 The concentration of threading dislocations averaged over the large area surface of a freestanding ammonothermal Group III nitride boule or wafer may be between about 10 7 cm -2 Less than, about 10 6 cm -2 Less than, about 10 5 cm -2 Less than, about 10 4 cm -2 Less than, about 10 3 cm -2 Less than or about 10 2 cm -2 The concentration of stacking faults averaged over a large area surface of a free-standing ammonothermal Group III nitride boule or wafer can be less than about 10 3 cm -1 Less than, about 10 2 cm -1Less than 10cm -1 Less than 1cm -1 Less than or about 0.1 cm -1 The thickness of the threading dislocations may be less than 100 μm, or may be undetectable. In some embodiments, for example, after repeated regrowth and / or growth to a thickness of more than 2 mm, more than 3 mm, more than 5 mm, or more than 10 mm on a seed crystal having a patterned array of dislocations, the location of the threading dislocations may shift somewhat laterally relative to the pattern of the seed crystal. In such cases, the region of higher concentration of threading dislocations may be somewhat more diffuse than the relatively sharp lines shown generally in FIGS. 5A-5E. However, the concentration of threading dislocations as a function of lateral position along the line on the surface varies periodically with a period between about 5 micrometers and about 20 mm, or between about 200 micrometers and about 5 mm. The concentration of threading dislocations in the periodically varying regions may vary by at least 2-fold, at least 5-fold, at least 10-fold, at least 30-fold, at least 100-fold, at least 300-fold, or at least 1000-fold.

[0047] Free-standing ammonothermal Group III metal nitride boules or wafers have been fabricated with the following surface configurations: (0001)+c-plane, (000-1)-c-plane, {10-10}m-plane, {11-20}a-plane, {11-2±2}, {60-6±1}, {50-5±1}, {40-4±1}, {30-3±1}, {50-5±2}, {70-7±3}, {20-2±1}, {3 The large area crystal orientation may be within 5 degrees, 2 degrees, 1 degree, 0.5 degrees, 0.2 degrees, 0.1 degrees, 0.05 degrees, 0.02 degrees, or 0.01 degrees of {0-3±2}, {40-4±3}, {50-5±4}, {10-1±1}, {10-1±2}, {10-1±3}, {21-3±1}, or {30-3±4}. The free-standing ammonothermal Group III metal nitride boule or wafer may have a (hkil) semipolar large area surface orientation, where i=-(h+k) and l, and at least one of h and k is nonzero.

[0048] In certain embodiments, the large area surface of the freestanding ammonothermal Group III metal nitride crystal or wafer has a miscut crystallographic orientation between about -60 degrees and about +60 degrees from the {10-10}m-plane in the

[0001] +c direction and up to about 10 degrees in the orthogonal <1-210>a direction. In certain embodiments, the large area surface of the freestanding ammonothermal Group III metal nitride crystal or wafer has a miscut crystallographic orientation between about -30 degrees and about +30 degrees from the {10-10}m-plane in the

[0001] +c direction and up to about 5 degrees in the orthogonal <1-210>a direction. In one particular embodiment, the large area surface of a freestanding ammonothermal Group III metal nitride crystal or wafer has a miscut crystallographic orientation from about −5 degrees to about +5 degrees from the {10-10} m-plane toward the

[0001] +c direction and up to about 1 degree toward the orthogonal <1-210> a direction. In certain embodiments, the large area surface of the freestanding ammonothermal Group III metal nitride crystal or wafer has a crystallographic orientation miscut by between about -5 degrees and about +5 degrees, between about -1 degree and about +1 degree, between about -0.5 degrees and about +0.5 degrees, or between about -0.25 degrees and about +0.25 degrees toward the

[0001] +c direction, and by up to about 1 degree, up to about 0.3 degrees, up to about 0.1 degrees, or up to about 0.05 degrees toward the orthogonal <1-210>a direction, from a semipolar plane selected from one of {10-1±1}, {20-2±1}, {30-3±1}, or {60-6±1}. 2 cm -1 Less than 10cm -1 Less than or equal to 1 cm -1 and a stacking fault concentration of less than about 10 on one or both of the two large area surfaces. 5 cm -2 Less than, about 10 4 cm -2 Less than, about 10 3 cm -2 Less than, about 10 2 cm -2 Less than or about 10cm -2 It may have a very low dislocation density of less than 100 nm.

[0049] A free-standing ammonothermal Group III metal nitride boule or wafer may have a symmetric x-ray rocking curve full width at half maximum (FWHM) of less than about 200 arc seconds, less than about 100 arc seconds, less than about 50 arc seconds, less than about 35 arc seconds, less than about 25 arc seconds, or less than about 15 arc seconds. A free-standing ammonothermal Group III metal nitride boule or wafer may have a crystallographic radius of curvature of greater than 0.1 meter, greater than 1 meter, greater than 10 meters, greater than 100 meters, or greater than 1000 meters in at least one, at least two, or three independent or orthogonal directions.

[0050] In one particular embodiment, at least one surface of a free-standing ammonothermal Group III metal nitride boule or wafer has a surface area of ​​about 1×10 16 cm -3 Exceeding approx. 1×10 17 cm -3 More than or about 1×10 18 cm -3 In certain embodiments, the ratio of the atomic impurity concentration of H to the atomic impurity concentration of O is between about 0.3 and about 1000, between about 0.35 and about 10, between about 0.4 and about 3, between about 0.5 and 1.0, or between about 10 and about 100. In certain embodiments, at least one surface of the freestanding ammonothermal Group III metal nitride boule or wafer has an impurity concentration of at least one of lithium (Li), sodium (Na), potassium (K), fluorine (F), chlorine (Cl), bromine (Br), or iodine (I) greater than about 1×10 15 cm -3 Super, about 1×10 16 cm -3 More than or about 1 x 10 17 cm -3 Super, about 1×10 18 cm -3 In one particular embodiment, the top and bottom surfaces of a free-standing ammonothermal Group III metal nitride boule or wafer have impurity concentrations of O, H, carbon (C), Na, and K of about 1×10, respectively, as quantified by calibrated secondary ion mass spectrometry (SIMS).16 cm -3 From 5×10 19 cm -3 Between, about 1 × 10 16 cm -3 From 8×10 19 cm -3 Between 1×10 17 cm -3 Less than 1×10 16 cm -3 Less than or equal to 1 x 10 16 cm -3 In another embodiment, the top and bottom surfaces of the freestanding ammonothermal Group III metal nitride boule or wafer may each have an impurity concentration of about 1×10, ... 16 cm -3 From 1×10 19 cm -3 Between, about 1 × 10 16 cm -3 From 2 × 10 19 cm -3 Between 1×10 17 cm -3 Less than and about 3 x 10 15 cm -3 From 1×10 18 cm -3 In yet another embodiment, the top and bottom surfaces of the freestanding ammonothermal Group III metal nitride boule or wafer may have impurity concentrations of O, H, C, and at least one of F and Cl of between about 1×10 and 1×10, respectively, as quantified by calibrated secondary ion mass spectrometry (SIMS). 16 cm -3 From 5×10 19 cm -3 Between, about 1 × 10 16 cm -3 From 8×10 19 cm -3 Between 1×10 17 cm -3 Less than and about 1 x 10 15 cm -3 From 1×10 19 cm -3In some embodiments, the top and bottom surfaces of the freestanding ammonothermal Group III metal nitride boules or wafers have an impurity concentration of H of between about 5×10, as quantified by calibrated secondary ion mass spectrometry (SIMS). 17 cm -3 From 3×10 19 cm -3 In certain embodiments, the top and bottom surfaces of the freestanding ammonothermal Group III metal nitride boule or wafer can have an F to O impurity ratio of between about 0.01% and about 25%, between about 0.1% and about 10%, or between about 0.3% and about 5%. In certain embodiments, at least one surface of the freestanding ammonothermal Group III metal nitride boule or wafer can have an F to O impurity ratio of between about 1×10 16 cm -3 From 1×10 19 cm -3 In a particular embodiment, the free-standing ammonothermal Group III metal nitride boule or wafer has an impurity concentration of copper (Cu), manganese (Mn), and iron (Fe) between about 3175 cm -1 It has an infrared absorption peak at 100 nm and its absorbance per unit thickness is about 0.01 cm -1 Exceeds.

[0051] The free-standing ammonothermal Group III metal nitride crystals or wafers may be characterized by a wurtzite structure that is substantially free of cubic or other crystal structures, with other crystal structures comprising less than about 0.1% by volume of the substantially wurtzite structure.

[0052] Surprisingly, given the lattice mismatch between HVPE GaN and ammonothermal GaN, results from the use of the techniques disclosed herein show that ammonothermal lateral epitaxial overgrowth can produce thick, large area GaN layers that are crack-free. In certain embodiments, the freestanding ammonothermal Group III metal nitride crystals or wafers have diameters of greater than about 25 millimeters, greater than about 50 millimeters, greater than about 75 millimeters, greater than about 100 millimeters, greater than about 150 millimeters, greater than about 200 millimeters, greater than about 300 millimeters, or greater than about 600 millimeters, and thicknesses of greater than about 0.1 millimeters, greater than about 0.2 millimeters, greater than about 0.3 millimeters, greater than about 0.5 millimeters, greater than about 1 millimeter, greater than about 2 millimeters, greater than about 3 millimeters, greater than about 5 millimeters, greater than about 10 millimeters, or greater than about 20 millimeters, and are substantially crack-free. In contrast, we found that ammonothermal growth on large-area unpatterned HVPE GaN seeds cracks when the layers are thicker than a few hundred micrometers, even if a patterning process was used to form the HVPE GaN seeds.

[0053] The freestanding ammonothermal Group III metal nitride wafers may be characterized by a total thickness variation (TTV) of less than about 25 micrometers, less than about 10 micrometers, less than about 5 micrometers, less than about 2 micrometers, or less than about 1 micrometer, and a macroscopic bow that is less than about 200 micrometers, less than about 100 micrometers, less than about 50 micrometers, less than about 25 micrometers, or less than about 10 micrometers. The large area surfaces of the freestanding ammonothermal Group III metal nitride wafers may have diameters or characteristic dimensions of greater than about 100 micrometers or less than about 2 cm. -2 Less than 1cm -2 Less than 0.5cm -2 Less than 0.25cm -2 Less than or about 0.1 cm -2The free-standing ammonothermal Group III metal nitride crystal or wafer may have a macrodefect concentration of less than about 1×10. The variation in miscut angle across the large area surface of the free-standing ammonothermal Group III metal nitride crystal or wafer may be less than about 5 degrees, less than about 2 degrees, less than about 1 degree, less than about 0.5 degrees, less than about 0.2 degrees, less than about 0.1 degrees, less than about 0.05 degrees, or less than about 0.025 degrees in each of two orthogonal crystallographic directions. The free-standing ammonothermal Group III metal nitride wafer may have a root mean square surface roughness of less than about 0.5 nanometers, less than about 0.2 nanometers, less than about 0.15 nanometers, less than about 0.1 nanometers, or less than about 0.10 nanometers, measured over an area of ​​at least 10 μm×10 μm. The free-standing ammonothermal Group III metal nitride wafer may have a macrodefect concentration of less than about 1×10. 17 cm -3 From about 3 × 10 19 cm -3 and about 100 cm 2 / Vs. In an alternative embodiment, the free-standing ammonothermal Group III metal nitride wafer can be characterized by n-type electrical conductivity with a carrier mobility of greater than about 1×10 15 cm -3 From about 1×10 19 cm -3 In yet another embodiment, the freestanding ammonothermal Group III metal nitride wafer is characterized by semi-insulating electrical behavior and a room temperature resistivity of about 10 7 ohm-centimeters, approximately 10 8 ohm-centimeters, approximately 10 9 ohm-centimeters, approximately 10 10 More than or about 10 Ohm-Centimeter 11 In one particular embodiment, the freestanding ammonothermal Group III metal nitride wafer is highly transparent, with an optical absorption coefficient at a wavelength of 400 nanometers of approximately 10 cm -1 Less than 5cm -1 Less than 2cm -1 Less than 1cm -1 Less than 0.5cm -1 Less than 0.2cm-1 Less than or about 0.1 cm -1 is less than.

[0054] In some embodiments, the free-standing ammonothermal Group III metal nitride crystal or wafer is used as a seed crystal for further bulk growth. In one particular embodiment, the further bulk growth comprises ammonothermal bulk crystal growth. In another particular embodiment, the further bulk growth comprises high temperature solution crystal growth, also known as flux crystal growth. In yet another particular embodiment, the further bulk growth comprises HVPE. The further grown crystal can be sliced, lapped, ground, polished, etched, and / or chemically mechanically polished into wafers by methods known in the art. The surface of the wafer can be characterized by a root mean square surface roughness measured over an area of ​​10 micrometers by 10 micrometers that is less than about 1 nanometer or less than about 0.2 nanometers.

[0055] The wafer can be incorporated into a semiconductor structure. The semiconductor structure can include at least one Al x In y Ga (1-x-y)N epitaxial layer, where 0≦x, y, x+y≦1. The epitaxial layer may be deposited on the wafer according to methods known in the art, for example by metalorganic chemical vapor deposition (MOCVD) or molecular beam epitaxy (MBE). At least a portion of the semiconductor structure may form part of a gallium nitride based electronic or optoelectronic device, such as a light emitting diode, a laser diode, a power conversion photodiode, a photodetector, an avalanche photodiode, a photovoltaic, a solar cell, a water photoelectrochemical splitting cell, a transistor, a rectifier, and a thyristor; a transistor, a rectifier, a Schottky rectifier, a thyristor, a pin diode, a metal-semiconductor-metal diode, a high electron mobility transistor, a metal semiconductor field effect transistor, a metal oxide field effect transistor, a power metal oxide semiconductor field effect transistor, a power metal insulator semiconductor field effect transistor, a bipolar junction transistor, a metal insulator field effect transistor, a heterojunction bipolar transistor, a power insulated gate bipolar transistor, a power vertical junction field effect transistor, a cascode switch, an inner subband emitter, a quantum well infrared photodetector, a quantum dot infrared photodetector, and combinations thereof. The gallium nitride based electronic or optoelectronic device may be incorporated into a fixture, such as a lamp or a light fixture. Gallium nitride based electronic or optoelectronic devices may have lateral dimensions of at least 0.1 millimeters by 0.1 millimeters after singulation. Gallium nitride based electronic or optoelectronic devices may have maximum dimensions of at least 8 millimeters and may include, for example, laser diodes. Gallium nitride based electronic or optoelectronic devices may be completely dislocation-free throughout their entire volume. For example, 10 4 cm -2 With a dislocation density of 0.1 × 0.1 mm 2 It can be expected that a significant fraction of these devices will be free of dislocations. 2 cm -2 At a dislocation density of 1×1 mm 2A significant portion of a gallium nitride based electronic or optoelectronic device may be expected to be free of stacking faults throughout its volume. For example, a 1 cm -1 At stacking fault densities of 10 × 1 mm, a 10 × 1 mm laser diode with a nonpolar or semipolar large area surface and c-plane facets is 2 It can be expected that a significant portion of the striped devices will be free of stacking faults.

[0056] 6A, 6B, 7A, and 7B are cross-sectional views illustrating methods and resulting optoelectronic and electronic devices according to embodiments of the present disclosure. Two-terminal or three-terminal devices, such as optoelectronic or electronic devices, can be formed by a series of steps including depositing epitaxial layers on a free-standing ammonothermal group III metal nitride wafer 431 or on a substrate having a pattern of locally approximately linear arrays 419 of threading dislocations and including at least one AlInGaN active layer 631, for example by MOCVD, as shown in FIG. 6B. In a particular embodiment, the deposited layers include an n-type or n+ layer 633, a doped or unintentionally doped single quantum well (SQW), multiple quantum well (MQW) structure, double heterostructure (DH structure), or n drift layer 631, and a p-type layer 635, as shown. - The drift layer can be important, for example, in a vertical field effect transistor. The device structure can be vertical, as shown diagrammatically in FIG. 6B, or lateral, as shown diagrammatically in FIG. 7A. In operation, the device can be electrically connected to an external circuit to provide an electrical potential between the n-contact 639 and the p-contact 637. Additional layers can be deposited, such as a separate confinement heterostructure (SCH) layer, a cladding layer, an AlGaN electron blocking layer, and a p+ contact layer, among others. Often, threading dislocations in the substrate (e.g., wafer 431), such as the pattern of the locally approximately linear array 419, propagate into the deposited layers, potentially affecting the performance of the device.

[0057] In a particular embodiment, the method also deposits an n-type contact 639 and a p-type contact 637, as shown in Figures 6B and 7A. In some embodiments, at least one of the sets of n-type and p-type contacts is positioned with a particular alignment with respect to the coalescence front, the wing region, and / or the window region. The light emitting portion may be centered on or between the coalescence fronts. In one particular embodiment, a transparent p-type contact is deposited and positioned to avoid contact with the coalescence front, which may have a high threading dislocation concentration. In this manner, a light emitting structure or photodiode structure with a relatively low concentration of threading dislocations can be formed. In this manner, a light emitting structure, PN diode, photodiode, or Schottky barrier diode with a relatively low concentration of threading dislocations can be formed. In a preferred embodiment, the light emission and / or maximum electric field region is designed to overlap the wing region 417 and to avoid a locally approximately linear array 419 pattern. In a particular embodiment, the defect region associated with the coalescence front or the window region is utilized as a shunt path to reduce the series resistance. In one particular embodiment, the n-type contact is 3 cm -1 and / or an edge dislocation density of about 10 5 cm -2 are located above the coalescence front or window region with a threading dislocation density exceeding

[0058] 7A, in some embodiments, such as laser diodes, PN diodes, photodiodes, or Schottky barrier diodes, the p-contact can be placed in an area that is substantially free of the coalescence front. In certain embodiments, such as laser diodes, a laser ridge or stripe structure 740 can be placed in an area that is substantially free of the coalescence front. A mesa can be formed by conventional lithography and an n-type contact placed in electrical contact with the n-type layer and / or substrate. Additional structures, such as sidewall passivation, ion implanted regions, field plates, etc., can be placed in alignment with the coalescence front.

[0059] 7B, in some embodiments, such as, for example, a current apertured vertical electron transistor (CAVET), an n drift layer 731 is deposited on an n+ contact layer 730, which in turn is deposited on the free-standing fused ammonothermal group III metal nitride boule 413. A P-type layer 735 is formed on the n drift layer 731 with an aperture 732. Following the remaining regrowth of the n drift layer 731, an AlGaN 2D electron gas layer 736 is deposited. Finally, a source contact 737, a drain contact 739, a dielectric layer 741, and a gate contact 743 are deposited. In a preferred embodiment, the aperture 732 is positioned away from the coalescence front region of the locally nearly linear array 419. In a preferred embodiment, the aperture 732 is located away from the window region 415. In a preferred embodiment, the aperture 732 is located above the wing region 417. Other types of three terminal devices, such as trench CAVETs, MOSFETs, etc., are positioned so that the area of ​​maximum electric field is located within the wing region 417.

[0060] The inventors have discovered that many of the processes described above, including growth on unpatterned substrates, growth on conventionally masked patterned substrates, growth on trench-patterned substrates, certain wafer processing related machining processes, and device fabrication, can be facilitated by elevated oxygen concentrations and / or oxygen gradients within certain ranges in the GaN crystal, especially when the GaN crystal is grown primarily in the [0 0 0 -1] direction. The inventors have further discovered that similar gradients in hydrogen and fluorine, with H / O and F / O ratios within predetermined ranges, can also be desirably formed using the methods provided herein for forming oxygen gradients in GaN crystals.

[0061] The oxygen concentration and other impurity concentrations (including gradients) in GaN crystals can be effectively quantified using calibrated secondary ion mass spectrometry (SIMS). In one particular embodiment, the near-surface impurity concentration can be determined using, for example, Cs +A beam of primary ions, e.g., is rastered to a region of interest on a surface, and a secondary ion, e.g., O - , H - , or F - It can be quantified by measuring the signal due to the ions. In other embodiments, e.g., O + Using the beam + , K + , or Mg + can be detected. In certain embodiments, the primary ions are rastered over a square area between about 20 micrometers and about 300 micrometers on a side, or between about 50 micrometers and about 150 micrometers on a side. In certain embodiments, to avoid edge effects associated with the perimeter of ion beam induced sputter craters formed on the surface, secondary ion signals are collected only while the primary ions are rastered over a subset of the square area, for example, an area between about 10 micrometers and about 250 micrometers or between about 25 micrometers and about 150 micrometers. In certain embodiments, the SIMS signals are collected at sputter depths between about 0.5 micrometers and about 25 micrometers, between about 1 micrometer and about 20 micrometers, or between about 2 micrometers and about 10 micrometers. In certain embodiments, the SIMS signals are calibrated by performing similar measurements on crystals of similar composition and crystal orientation implanted with precisely known concentrations of oxygen, hydrogen, and / or fluorine. SIMS measurements can be performed on one, two, three, four, five, ten, or more regions of a surface, for example to measure average values ​​or to quantify gradients.

[0062] 8 illustrates a method for quantifying the oxygen and other impurity concentrations in a freestanding ammonothermal Group III metal nitride boule or wafer 431. In certain embodiments, the oxygen and other impurity concentrations can be determined at a first surface 841 and a second surface 843 opposite the first surface 841 of the freestanding ammonothermal Group III metal nitride boule or wafer 431 and spaced a thickness t from the first surface 841 using the SIMS techniques described above. In certain embodiments, the oxygen and other impurity concentrations and their gradients in the freestanding ammonothermal Group III metal nitride boule or wafer 431 can be quantified by making a first cross-cut 845 through the freestanding ammonothermal Group III metal nitride boule or wafer 431 at an angle α relative to the first surface 841, where α is between about 1 degree and 90 degrees, between about 2 degrees and about 90 degrees, or between about 4 degrees and about 30 degrees. The first cross cut 845 can be made using a single wire saw, a multi-wire saw, a dicing saw, an ID saw, an OD saw, grinding, or the like. In certain embodiments, a second cross cut 847 is also made generally parallel to the first cross cut 845. In certain embodiments, the cross cut surface 855 exposed by the first cross cut 845 is subjected to one or more of lapping, grinding, polishing, and chemical mechanical polishing. The oxygen concentration and other impurities along the cross cut surface 855 can be quantified at one or more points by SIMS as described above. The oxygen concentration and other impurities at one or more depths d relative to a reference plane 859 in the freestanding ammonothermal Group III metal nitride boule or wafer 431 can be quantified by performing SIMS measurements at one or more lateral positions w along the cross cut surface 855 relative to the intersection of the reference plane 859 and the cross cut surface 855, where the depth d is equal to the quantity w sin α. In one particular embodiment, the reference surface 859 is selected from one of the first surface 841 and the second surface 843.In one particular embodiment, the reference surface 859 is selected to be a regrowth interface, such as surface 102 of FIG. 1A, that can be easily visually identified along the surface cross-cut 855 by different colors, light absorption coefficients (levels of darkness), or fluorescent characteristics.

[0063] The wedge-shaped sample approach described above assumes that the impurity distribution within the boule or wafer 431 is quasi-one-dimensional, i.e., approximately uniform along a plane parallel to the first surface 841 and the second surface 843. This assumption should be valid if growth occurs primarily in a single crystal orientation perpendicular to the first surface 841 and / or the second surface 843. Modifications to the shape shown in FIG. 8 can be easily made by one skilled in the art if the first surface 841 and the second surface 843 have a different crystal orientation than the growth front, e.g., if the first surface 841 is prepared to have a controlled miscut with respect to (0 0 0 1) or (0 0 0 -1). In either case, the lateral uniformity of the impurity concentration, e.g., along the reference plane 859, can be experimentally quantified by making additional cuts parallel to the first crosscut 845 and the second crosscut 847.

[0064] Referring again to FIG. 8, a similar approach can be used to quantify the effectiveness of coalescence of laterally grown wings by preparing double normal cross-sections, i.e., by making a first cross-cut 845 and a second cross-cut 847 at an angle α=90° (see FIG. 2C and FIG. 3E). In a preferred embodiment, the first cross-cut 845 and the second cross-cut 847 are made in a plane perpendicular to the lateral growth direction, e.g., in the plane of the page of FIG. 2A-2C and FIG. 3A-3E. The cross-cut surface 855 can be polished and sliced ​​samples can be examined under an optical microscope using transmitted light. Different crystal sectors can be easily distinguished by color differences caused by differences in absorption of impurities.

[0065] An example of lateral growth and coalescence is shown in FIG. 9, which is a schematic diagram of an optical micrograph of a double-normal cross section of a GaN crystal with an angle α=90° (see FIG. 6). In the particular embodiment shown in FIG. 9, vertical growth occurs in the [0 0 0 -1] direction, and lateral growth occurs in the [1 1 -2 0] and [-1 -1 2 0] directions, with the [1 -1 0 0] direction extending outward from the plane of the page. During the growth process, the -c sector material 965 (item 213 in FIG. 2B) grew in the [0 0 0 -1] direction from the substrate 101 through the opening 112 in the patterned mask layer 111. After emerging from the opening 112, the material began to grow in the [1 1 -2 0] and [-1 -1 2 0] directions, forming the a sector material 967 (item 217 in FIG. 2C). The sector boundary 961 between the -c sector material 965 and the a sector material 967 can be easily observed by transmission or fluorescence microscopy because the a sector material 967 is lighter in color and has different fluorescent properties than the -c sector material 965 under normal visible illumination. During the crystal growth process, as the opposing laterally growing wing regions begin to approach each other, nutrients from the supercritical ammonia solvent may begin to have difficulty reaching the lateral growth front, forming a solvent-filled gap 963 between the opposing laterally growing wing regions, after which the a sector material 967 may begin to overgrow. Shortly after coalescence of the laterally grown wings occurs, the -c sector material 965 may overgrow relative to the a sector material 967. The coalescence front 219 is not usually visible in the double normal cross section, but can be observed as threading dislocations on the (0 0 0 -1) growth facet. The rate at which the laterally growing wings coalesce and are covered by -c sector material 965 can be quantified as the coalescence distance 969, defined as the separation between the surface 102 and a coalescence plane 959 that is parallel to the surface 102 of the substrate 101 and intersects the top of one or more a sector regions 967.

[0066] The coalescence distance 969 has been found to depend on many variables in the crystal growth process. Figure 10 shows the peak concentration of oxygen (in units of 10 ) in the grown GaN layer after subtracting contributions from other process variables such as the temperature distribution within the growth capsule, as measured by SIMS using the wedge sampling technique shown in Figure 8. 18 cm -3 10 is a schematic graph of the linear regression fit of coalescence distance 969 (in millimeters (y-axis)) versus peak oxygen concentration 969 (in millimeters (x-axis)). The P-value of the linear regression fit (0.0016) is well below 0.05, suggesting that this dependence on oxygen concentration is statistically significant. As is evident from FIG. 10, the coalescence distance increases with increasing peak oxygen concentration from 10 18 cm -3 The low to medium range of oxygen concentration is about 0.8 to 1 mm, while the peak oxygen concentration in the GaN layer is about 3.5×10 19 cm -3 , the coalescence distance decreases to about 0.2 mm.

[0067] Calibrated SIMS, in combination with the sample preparation techniques described above and in Figure 8, provides a way to directly determine the oxygen concentration and gradient in GaN crystals, but in some cases it may be more convenient to infer the oxygen concentration from optical absorption measurements. It is well known that oxygen doping increases the optical absorption coefficient of GaN. There are at least two contributions. First, oxygen doping increases the concentration of free carriers, which leads to sub-bandgap phonon-assisted optical absorption. Phonon-assisted optical absorption has been quantified by first-principles calculations by Kioupakis et al. [Phys. Rev. B 81, 241201 (R) (2010); Appl. Phys. Express 3, 082101 (2010)] and by direct measurements on GaN crystals grown by various growth techniques [Pimputkar, et al., J. Crystal Growth 432, 49 (2015)]. Second, it is well documented that gallium vacancies in complex with hydrogen and / or oxygen give rise to sub-bandgap optical absorption in ammonothermally grown GaN [e.g., Pimputkar, et al., J. Crystal Growth 432, 49 (2015); Jiang, et al., Appl. Phys. Express 10, 075506 (2017)].

[0068] Figure 11 shows the optical absorption coefficient α at a wavelength of 450 nm in the m-plane cross section of a GaN crystal grown ammonothermally in the [0 0 0 -1] direction. 450 The dependence of the absorption on the oxygen concentration is shown. The contribution of phonon-assisted free-carrier absorption was quantified by measuring the optical absorption coefficient at 539 nm (2.3 eV) for the same cross section and assigning the latter to phonon-assisted free-carrier absorption using the parameterization reported by Kioupakis et al. The optical absorption coefficient is proportional to the oxygen concentration, which is a very good approximation, and on average, about half of the absorption at 450 nm is due to phonon-assisted free-carrier absorption. The remainder of the optical absorption is due to gallium vacancy complexes with hydrogen and / or oxygen [e.g., Jiang, et al., Appl. Phys. Express 10, 075506 (2017)].

[0069] In the ideal case, growth on an unpatterned or patterned seed produces an as-grown boule with a smooth, flat surface (e.g., a (0 0 0 -1) facet), as shown generally in Figures 1A, 2C, and 3E. In some cases, however, growth produces some regions that are smooth and other regions that are rough, as shown generally in Figure 12. Figure 12 is a schematic diagram of an as-grown boule 1200 having a (0 0 0 -1) top surface and {1 0 -1 -1} side facets. Portion 1271 of the (0 0 0 -1) top surface has a smooth morphology and portion 1273 has a rough morphology, separated by boundary 1275. The root mean square (rms) surface roughness in portion 1271 may be between about 0.1 nanometers and about 50 micrometers, or between about 10 nanometers and about 10 micrometers, and may include regions dominated by step growth, including both single and multiple steps. The smooth morphology indicates that growth proceeds primarily in the [0 0 0 -1] direction, impurity concentrations may be relatively uniform, and minimal yield loss may occur during wafer processing operations. The root mean square surface roughness in portion 1273 may be between about 10 micrometers and about 10 millimeters, between about 50 micrometers and about 5 millimeters, or between about 100 micrometers and about 2 millimeters. Morphological features in portion 1273 may include one or more of incompletely coalesced trenches, macroscopic step bunching growth, cellular growth, hillocks, depressions, or dendritic growth. This rough morphology suggests that in these regions growth may not occur primarily in the [0 0 0 -1] direction, there may be large lateral and axial variations in impurity concentration, large stresses may be present, and large yield losses may occur during wafer processing operations such as sawing, grinding, and polishing.

[0070] The maximum oxygen concentration of the growing boule, regardless of other factors, or equivalently, the maximum optical absorption coefficient α at 450 nm450 (see Fig. 11) was found to have a significant effect on the proportion of growing (0 0 0 -1) facets that grow with a smooth rather than a rough surface morphology, as shown in Fig. 13. For patterned growth, the average area fraction of the (0 0 0 -1) facets with a smooth morphology was found to be α 450 The maximum value of about 4 (or the peak oxygen concentration of about 8×10 18 cm -3 ,Figure 11) from about 40%. 450 The maximum value of exceeds 15 (or the peak oxygen concentration is about 3 × 10 19 cm -3 The effect of patterned growth is similar, but smaller, with the percentage of smooth regions increasing over a similar range from about 70% to about 90%.

[0071] Without wishing to be bound by theory, the inventors believe that several mechanisms involving oxygen contribute to the effect shown in FIG. 13. First, for patterned growth, the initial presence of oxygen in the growth environment before coalescence occurs reduces the growth thickness required for coalescence (FIG. 10). Second, we have found that in addition to increasing the ratio of the growth rates in the a-direction to the -c-direction (see FIGS. 9 and 10), oxygen also increases the ratio of the growth rate in the m-direction to the growth rate in the -c-direction, as shown in FIG. 14. For the data shown in FIG. 14, many other factors also contribute to the growth rate ratio, as indicated by an R-squared value of only 0.41, but the effect of oxygen is also evident, as indicated by a P value of about 0.0002. For an average oxygen concentration of about 2×10 18 cm -3 From about 4 × 10 19 cm -3 The growth rate ratio increases from about 0.3 to about 0.6 as the oxygen concentration increases. The combination of these first two effects indicates that for growth in the -c direction, the ratio of the lateral to vertical growth rate increases with increasing oxygen concentration, resulting in a flatter growth front and a smoother surface.

[0072] A third mechanism by which oxygen and oxygen gradients may benefit the crystal growth process is shown diagrammatically in FIG. 15. In an ideal seed crystal, the Ga and N atoms lie in perfectly flat planes with an infinite crystallographic radius of curvature. As growth progresses, the Ga and N atoms may simply continue to incorporate into these planes without an increase in stress. However, in real seeds, such as those derived from heteroepitaxial growth processes, residual stresses, mosaic structures, or other defects may exist that result in a non-infinite radius of curvature. As growth progresses on such seeds, stresses may increase as growth proceeds in the vertical direction, disrupting the continuity of the Ga-N planes in one or more ways. In some cases, the increased stresses may disrupt the planarity of the growth front because the crystal can lower its free energy by adopting a three-dimensional growth form, such as cellular growth. In some cases, the increased stresses may be relieved by the formation of cracks. However, in the presence of heteroatoms that slightly change the lattice constant when incorporated, such as oxygen, these stresses may be relieved without disrupting the continuity of the Ga-N planes. In particular, a controlled oxygen gradient can gradually relieve stress and improve the crystal planarity, resulting in a more ideal Ga-N surface.

[0073] Hydrogen and fluorine concentration gradients that accompany the oxygen gradient may also contribute to these effects.

[0074] In addition to benefits in preparing free-standing ammonothermal Group III metal nitride boules and wafers, controlling the oxygen concentration and gradient can also provide benefits in devices fabricated on these substrates, as shown in Figures 6A, 6B, 7A, and 7B. In many cases, the oxygen concentration directly beneath n-type layer 633 or 730 should be kept below 3 x 10 to minimize resistive losses during device operation, especially at high current densities, and especially as substrates become thinner during device processing. 18 cm -3 Super, 5×10 18 cm -3 Super, 1×10 19 cm -3 Over or 3 x 10 19cm -3 It is desirable to have an n-contact on the (0 0 0 1) side of the substrate. Additionally, devices with n-contacts on the (0 0 0 1) side of the substrate may benefit from reduced contact resistance. Examples of such devices include N-face transistor devices (e.g., FIG. 7B and related discussion) and lateral Ga-face laser diodes.

[0075] The maximum oxygen concentration in free-standing ammonothermal GaN substrates is 5×10 19 cm -3 Or 1×10 20 cm -3 Above this, the optical absorption coefficient becomes so high that it degrades the performance of optical devices fabricated on the substrate, and the thermal conductivity is also adversely affected, which may degrade the performance of high power devices fabricated on the substrate. Thus, the maximum oxygen concentration in a free-standing ammonothermal Group III metal nitride boule or wafer, for example on the (0 0 0 1) surface, is approximately 1×10 20 cm -3 Less than 5×10 19 cm -3 Less than or about 3 x 10 19 cm -3 Less than 2×10 19 cm -3 Less than or about 1 x 10 19 cm -3 The minimum oxygen concentration for free-standing ammonothermal GaN crystals can be selected to be less than about 2×10 18 cm -3 Less than 1×10 18 cm -3 Less than or about 5 x 10 17 cm -3 If the oxygen concentration drops below about 2×10, the electrical resistivity will increase and ohmic losses will become significant in devices fabricated on the substrate, which may reduce the yield of substrate preparation and lead to undesirably high manufacturing costs. Thus, the minimum oxygen concentration for free-standing ammonothermal Group III metal nitride boules can be reduced to about 2×10 by using one or more of the following techniques: 18 cm -3 Super, about 1×10 18 cm -3 More than or about 5 x 1017 cm -3 If the maximum oxygen gradient in the [0 0 0 1] direction becomes too large, for example, about 1 × 10 21 cm -4 Exceeding approx. 5×10 20 cm -4 More than or about 2×10 20 cm -4 Above this, the stresses in the crystal become so large that they may crack spontaneously or during wafer fabrication. Thus, the maximum oxygen concentration gradient in the [0 0 0 1] direction in a free-standing ammonothermal Group III metal nitride boule can be reduced to approximately 1×10 21 cm -4 Less than 5×10 20 cm -4 Less than or about 2 x 10 20 cm -4 If the oxygen gradient is too low, for example, about 1 x 10 18 cm -4 Less than 5×10 17 cm -4 Less than 2×10 17 cm -4 Less than or about 5 x 10 16 cm -4 Below this, excessive residual stresses may remain from non-ideal seeds or yields in preparing the substrate may be reduced, resulting in undesirably high manufacturing costs. Thus, the minimum oxygen concentration gradient for a free-standing ammonothermal Group III metal nitride boule in the [0 0 0 1] direction can be reduced to about 5×10 by using one or more of the following techniques: 16 cm -4 Super, about 2×10 17 cm -4 Super, about 5×10 17 cm -4 More than or about 1 x 10 18 cm -4 Can be adjusted to ultra.

[0076] Oxygen concentrations and oxygen concentration gradients within the above beneficial ranges can be achieved by one or more of the methods described below. In one particular embodiment, as described in detail above, growth on the seed crystal occurs primarily in the [0 0 0 -1] direction using ammonothermal techniques. As the ammonothermal crystal growth process proceeds, the polycrystalline group III metal nutrient dissolves and the dissolved material is transported to the seed crystal where it is deposited as a single crystal layer. At the same time, oxygen present in the polycrystalline nutrient is released to the ammonothermal growth environment and available for incorporation into the growing group III metal nitride layer. As long as the oxygen concentration in the polycrystalline group III metal nitride nutrient is uniform and constant, the oxygen concentration incorporated in the growing [0 0 0 -1] sector will be uniform and constant as well. However, at the beginning of a growth run, as long as oxygen becomes available in the ammonothermal growth environment in excess of the steady-state amount present during the nutrient dissolution and crystal growth process, high concentrations of oxygen may be incorporated into the initial growing layer. If the high levels of oxygen are not fully replenished by nutrient dissolution, the oxygen concentration in the ammonothermal growth environment will decrease over time due to oxygen consumption by the growing Group III metal nitride crystal itself, creating a negative oxygen gradient in the [0 0 0 -1] direction within the growing crystal.

[0077] Several process conditions can be selected to generate and control high concentrations of oxygen at the beginning of an ammonothermal crystal growth run. In certain embodiments, the nutrient material is selected to be a polycrystalline material having a porosity between about 0.01 percent and about 10 percent, or between about 0.1 percent and about 5 percent, by volume, as quantified, for example, by mercury porosimetry. The amount of oxygen in the nutrient material can be controlled by controlling the purity of one or more of the raw materials (e.g., Ga metal and gas), the time and temperature of a bake-out procedure applied prior to the formation of the polycrystalline nutrient material, and intentional oxygen doping (e.g., adding H2O and / or O2 to one or more of the input gases used to form the polycrystalline nutrient material). After formation, the polycrystalline nutrient material can be cleaned by washing with acids, bases, oxidizing agents, etc., and residual water may be present in the pores after the washing process. In some embodiments, the amount of residual moisture in the polycrystalline nutrient material can be controlled by baking one or more of the polycrystalline nutrient materials themselves, or a sealable container, such as a capsule or autoclave, in which the polycrystalline nutrient material is placed, at a temperature between about 50° C. and about 600° C., between about 100° C. and about 400° C., or between about 150° C. and about 250° C. for a period of about 1 hour to about 96 hours prior to adding ammonia to the sealable container. Any moisture remaining in the polycrystalline nutrient material is released into the ammonothermal growth environment very early in the growth run, causing an increase in the oxygen concentration in the initially grown Group III metal nitride layer, which then gradually decreases. The magnitude of the increased oxygen concentration can be controlled by adjusting the porosity of the polycrystalline Group III metal nitride and the bakeout temperature and time.

[0078] Similarly, an oxide, e.g., Ga2O3, can be formed on the surface of a polycrystalline Group III metal nitride by heating in an oxidizing acid, such as 10% HNO3 in H2SO4 or HClO4, to a temperature between about 25°C and about 200°C for about 0.5 to about 10 hours, or in O2 or air, to a temperature between about 300°C and about 1000°C, or between about 500°C and about 850°C, for about 1 to about 24 hours. During the initial stages of ammonothermal growth, metal oxides, such as Ga2O3, react rapidly with NH3 to form metal nitride and H2O, which can be utilized to initially form a high oxygen concentration within the growing Group III metal nitride crystal. Thus, the relative amount of oxygen present during the initial stages of ammonothermal growth can be controlled by controlling or adjusting the thickness of the metal oxide layer formed on the polycrystalline Group III metal nitride.

[0079] In certain embodiments, polycrystalline nutrient material having relatively large grains, e.g., between about 50 micrometers and about 5 millimeters, is provided along with polycrystalline nutrient material having relatively small grains, e.g., between about 1 micrometer and about 25 micrometers. Grain boundaries may be oxygen rich, e.g., Ga2O3, and may be preferentially etched early in the crystal growth process, resulting in an initial high oxygen concentration in the growth environment and in the growing GaN layer. In certain embodiments, for example, about 3×10 18 cm -3 From about 1×10 20 cm -3The fine-grained polycrystalline nutrient material is intentionally doped with oxygen to a concentration between 0.1 and 0.2. The maximum oxygen concentration and the magnitude of the oxygen gradient can be adjusted by controlling the relative amounts of large and small grain polycrystalline nutrient material, as well as the oxygen concentration in the large and fine grain polycrystalline nutrient material and at the grain boundaries. In certain embodiments, a relatively small grain polycrystalline nutrient material or oxygen-doped nutrient material is placed in a sealable ammonothermal container where the nutrient material is to be etched first, so that the large grain nutrient material with a lower oxygen content can be etched later in the growth process. For example, in an ammonothermal process with inverse solubility, a nutrient material with a high oxygen content can be physically placed above a nutrient material with a low oxygen content (e.g., in a cooler region of the nutrient material region of the chamber) and in an area where the applied temperature is lower than the temperature of the nutrient material with a low oxygen content, such that the nutrient material with a high oxygen content is preferentially etched during the early stages of growth.

[0080] In certain embodiments, the timing of oxygen release, and therefore the oxygen gradient of the grown boule, can be controlled by introducing etchable barriers or structures within the nutrient source zone. When these barriers dissolve, they can allow communication between the dissolving fluid and certain volumes or regions of nutrient or other materials with desired composition, physical structure, and / or particle size. These exposed regions may contain materials with one or more selected oxygen concentrations or selected oxygen release rates due to differences in porosity, particle size, etc. In certain embodiments, a plate of polycrystalline GaN may act as an etchable barrier. In certain embodiments, the etchable barrier or structure is provided as a cover for the crucible. In certain embodiments, the crucible is made of or includes silver, gold, platinum, palladium, copper, nickel, and molybdenum. In certain embodiments, polycrystalline nutrient materials with low oxygen content are placed within the crucible and loaded into the sealable container prior to ammonothermal crystal growth.

[0081] In a particular embodiment, silver metal is present in the ammonothermal crystal growth environment. In a particular embodiment, the capsule within which the ammonothermal crystal growth environment is formed is composed of or includes silver. It is well known that silver can dissolve significant amounts of oxygen, and oxygen is readily permeable through silver at temperatures above 500° C. or 600° C., for example. In a particular embodiment, silver metal having an oxygen concentration of between about 10 ppm and about 200 ppm, or between about 20 ppm and about 100 ppm is provided to the ammonothermal growth environment, such that the ratio of the weight of silver to the weight of the polycrystalline group III metal nitride nutrient material is between about 0.01 and about 10, between about 0.1 and about 5, or between about 0.3 and about 2. During the initial stages of the crystal growth process, the temperature of the silver in contact with the supercritical ammonia increases above about 500° C., and oxygen diffuses from the silver into the growth environment, creating an initially high oxygen concentration in the growth environment and in the growing GaN layer. The presence of a coating at the interface between the silver and ammonia in the processing environment can reduce the diffusion rate. In certain embodiments, the coating comprises or consists of one or more of gold, platinum, or palladium. The maximum oxygen concentration and the magnitude of the oxygen gradient can be tuned by controlling the oxygen concentration in the silver, the ratio of the weight of silver to the weight of polycrystalline GaN, and the composition and thickness of the coating on the silver.

[0082] In certain embodiments, the oxygen content of the silver component in the sealable container, including one or more of the capsule, at least one baffle, a fixture for supporting the seed crystal, and other components, is minimized, allowing for more precise oxygen control by other process factors. In certain embodiments, the oxygen content of the silver component is minimized, for example, kept below 10 ppm or below 5 ppm, by one or more of reusing the silver component from a previous crystal growth run under supercritical ammonia or by calcining to a temperature between 400° C. and 950° C. in a suitable atmosphere. In certain embodiments, the calcination atmosphere comprises or consists of an inert gas, such as nitrogen, argon, or helium. In certain embodiments, the calcination atmosphere comprises more than 1%, more than 2%, or more than 4% hydrogen or ammonia. In certain embodiments, the calcination atmosphere comprises less than 6% hydrogen or ammonia. In certain embodiments, all welding operations involving silver components in a sealable container are performed under an inert atmosphere, such as argon or nitrogen, with an oxygen content of less than 1% or less than 0.1%, or in close proximity to a getter, such as graphite foil. In certain embodiments, the graphite foil is placed on the backside of the weld, in direct contact with one or more silver components, or with a gap of less than 2 millimeters, less than 1 millimeter, or less than 0.5 millimeters. In certain embodiments, the graphite foil is covered with a metal foil, such as stainless steel, to prevent direct exposure of the graphite foil to air.

[0083] In one particular embodiment, HO is metered and added to the sealable container after the optional bake-out step and before or after the addition of ammonia. In the early stages of the crystal growth process, the added HO is available to dope the growing GaN layer to a higher level compared to GaN layers formed later in the growth run. The maximum oxygen concentration and the magnitude of the oxygen gradient can be adjusted by controlling the weight of the added HO.

[0084] In certain embodiments, Ga2O3 is weighed and added to a sealable container along with the polycrystalline group III metal nitride. In certain embodiments, Ga2O3 is comprised of or includes a powder, grit, or polycrystalline ceramic. In the early stages of the crystal growth process, Ga2O3 can react with NH3 to form GaN (which may then dissolve) and H2O, the latter of which can be utilized to dope the growing GaN layer at a higher level compared to GaN layers formed later in the growth run. The maximum oxygen concentration and the magnitude of the oxygen gradient can be adjusted by controlling the weight of Ga2O3 added, the particle size of the powder or grit, and the particle size and porosity of the ceramic, the latter factors affecting the dissolution / reaction rate of Ga2O3 with NH3.

[0085] Other factors may also contribute to the maximum oxygen concentration and oxygen gradient, as well as the maximum hydrogen and fluorine concentrations and their gradients. For example, the purity of the ammonia and mineralizer(s) used may be controlled to introduce a targeted amount of impurities into the growth environment. The concentration of Ga vacancies and the ratio of the number of hydrogen atoms complexed therewith to the oxygen concentration may depend on the growth temperature. Although the atomic structure of fluorine in ammonothermal GaN appears to be poorly understood, fluorine may exist in nitrogen vacancies, and its concentration relative to oxygen may also depend on other growth-related conditions such as growth temperature and supersaturation. Supersaturation, growth rate, and growth initiation temperature may also affect the absorption of oxygen, hydrogen, and fluorine and their ratios.

[0086] In certain embodiments, the ratio of hydrogen concentration to oxygen concentration measured at discrete areas and averaged over at least a portion of the surface of the GaN crystal, wafer, or boule is between about 0.3 and about 10, between about 0.4 and about 5, or between about 0.5 and about 3. In certain embodiments, the ratio of fluorine concentration to oxygen concentration measured at discrete areas and averaged over at least a portion of the surface of the GaN crystal, wafer, or boule is between about 0.05% and about 10%, between about 0.1% and about 6%, or between about 0.2% and about 1%.

[0087] The oxygen concentration as a function of depth within a GaN crystal, wafer, or boule can be increased, for example, to about 10 at a depth between about 0.1 micrometers and about 10 micrometers using ion implantation. 16 cm -2 About 10 20 cm -2 The ion dose or fluence of oxygen ions can be modified by oxygen implantation or by treatment with an oxygen-containing plasma. The implantation of oxygen ions can cause damage to the crystal lattice, for example vacancies and interstitial defects, and can simultaneously cause stresses. These stresses can provide benefits in controlling warpage and / or curvature of the crystal, and can also help counter other stress sources. However, damage associated with ion implantation or plasma treatment can have many undesirable effects, including risk of delamination within the damaged layer, risk of property changes during thermal treatments, including growth of one or more epitaxial layers by MOCVD or MBE, degradation of electrical properties, and degradation of thermal properties. In preferred embodiments, the GaN crystals, wafers, and boules of the present disclosure are not ion implanted or plasma treated and are substantially free of damage from ion implantation or plasma.

[0088] By controlling the maximum concentration of oxygen and the oxygen gradient within the freestanding ammonothermal GaN boule, wafers with designed oxygen profiles can be prepared with good yield. For example, c-plane wafers having a first surface with a crystal orientation within 10 degrees, within 5 degrees, within 2 degrees, or within 1 degree of (0001) can be prepared using the above method. The wafers can have a diameter of at least 40 millimeters, at least 70 millimeters, at least 90 millimeters, at least 140 millimeters, or at least 190 millimeters, and a thickness of between about 200 micrometers and about 2000 micrometers, between about 225 micrometers and about 1000 micrometers, or between about 250 micrometers and about 600 micrometers. As quantified by calibrated secondary ion mass spectrometry, the average oxygen concentration within a depth of 2 to 10 micrometers on the first surface can be about 1.1 to about 10 times, or about 1.1 to about 3 times, greater than the average oxygen concentration within a depth of 2 to 10 micrometers on the opposite surface. The first surface can have a diameter of at least about 10 3 cm -1 Less than, about 10 2 cm -1 Less than 10cm -1 Less than or about 1 cm -1 The wafers may be characterized by a stacking fault concentration of less than about 30 microns, less than about 20 microns, less than about 10 microns, or less than about 5 microns.

[0089] In another embodiment, the above method can be used to prepare a non-polar or semi-polar wafer having a first surface with a crystallographic orientation within 30 degrees of {10-10}, a maximum dimension in a first direction that is greater than 5 millimeters, the first direction including a projection of [0 0 0 1] on the first surface, and a maximum dimension in a second direction perpendicular to the first direction that is greater than 15 millimeters. The wafer can have a thickness between about 100 micrometers and about 1000 micrometers, or between about 200 micrometers and about 600 micrometers. Due to the presence of an oxygen gradient in the [0 0 0 1] direction, the wafer has an optical absorption coefficient at a wavelength of 450 nanometers measured by scanning in the first direction of less than about 0.1 cm at a first location along the first surface. -1 About 5cm from -1 Between 0.01 and 0.02 inches (0.25 cm) -1 About 3cm from -1 and at a second location along the first direction, has a minimum value between about 0.5 cm -1 Approximately 25cm from -1 Between the two, approximately 0.75 cm -1 About 10cm from -1 Between or about 1 cm -1 About 6cm from -1 and the second location is separated from the first location by a distance of between 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters in the first direction. In certain embodiments, the crystal from which the wafer was prepared has been regrown one, two, three, or more times using the techniques described above. In certain embodiments, the wafer can be characterized by two, three, four, or more maxima and minima in the optical absorption coefficient at a wavelength of 450 nanometers and in the oxygen concentration measured by calibrated secondary ion mass spectrometry (SIMS) along the first direction. In certain embodiments, the wafer can be characterized by an optical absorption coefficient at a wavelength of 450 nanometers of between about 0.1 cm and about 0.2 cm at a third location along the first direction. -1 About 5cm from -1 Between 0.01 and 0.02 inches (0.25 cm) -1 About 3cm from -1and the third location is separated from the second location in the first direction by a distance of between about 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters. In one particular embodiment, the wafer is separated from the second location along the first direction by a distance of between about 0.5 cm and about 0.5 mm. -1 Approximately 25cm from -1 Between the two, approximately 0.75 cm -1 About 10cm from -1 Between or about 1 cm -1 About 6cm from -1 and the fourth location is separated in the first direction from the third location by a distance of between about 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters. The presence of an oxygen gradient in the [0 0 0 1] direction may cause the wafer to have an oxygen concentration measured when scanned in the first direction that is greater than about 2×10 at the first location along the first surface. 17 cm -3 From about 1×10 19 cm -3 or about 5 x 10 17 cm -3 From about 6 × 10 18 cm -3 and at a second location along the first direction, 18 cm -3 From about 5 × 10 19 cm -3 Between, about 1.5 × 10 18 cm -3 From about 2 × 10 19 cm -3 or about 2 x 10 18 cm -3 from about 1.2 × 10 19 cm -3and the second location is separated from the first location in the first direction by a distance of between 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters. In certain embodiments, the crystal from which the wafer was prepared has been regrown one, two, three, or more times using the techniques described above. In certain embodiments, the wafer has a third location along the first direction with a crystal size of between about 2×10 and about 2×10. 17 cm -3 From about 1×10 19 cm -3 or about 5 x 10 17 cm -3 From about 6 × 10 18 cm -3 and the third location is separated from the second location in the first direction by a distance of between about 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters. In one particular embodiment, the wafer has an oxygen concentration having a local minimum between about 1×10 at a fourth location along the first direction and about 1×10 at a fourth location along the first direction. 18 cm -3 From about 5 × 10 19 cm -3 Between, about 1.5 × 10 18 cm -3 From about 2 × 10 19 cm -3 or about 2 x 10 18 cm -3 from about 1.2 × 10 19 cm -3 and the fourth location is separated in the first direction from the third location by a distance between 1 millimeter and 25 millimeters, or between about 2 millimeters and about 10 millimeters. 3 cm -1 Less than, about 10 2 cm -1 Less than 10cm -1 Less than or about 1 cm -1The wafers may be characterized by a stacking fault concentration of less than about 5 microns, less than about 4 microns, less than about 3 microns, or less than about 2 microns.

[0090] In certain embodiments, the above methods can be used to prepare non-polar or semi-polar wafers having a first surface with a crystallographic orientation within 30 degrees of {10-10}, a maximum dimension greater than 5 millimeters in a first direction, the first direction including a projection of [0 0 0 1] on the first surface, and a maximum dimension greater than 15 millimeters in a second direction orthogonal to the first direction. In certain embodiments, the spacing between {20-21} lattice planes as a function of position on the first surface along the first direction of the wafer can be determined from the 2θ value of the (201) X-ray reflection as the sample is translated in the first direction under the X-ray beam in the diffractometer using Bragg's equation and methods known in the art. Due to the presence of an oxygen gradient in the [0 0 0 1] direction, the wafer can be characterized by a {20-21} lattice spacing that varies with the local oxygen concentration. An example of this behavior is shown in FIG. 19. In one particular embodiment, the difference between the minimum {20-21} lattice spacing and the maximum {20-21} lattice spacing along the first direction is at least 2×10 -5 Å and 3×10 -4 Å or ​​less, or at least 4×10 -5 Å and 2×10 -4 In one particular embodiment, the separation between the local maximum {20-21} lattice constant and the local minimum {20-21} lattice constant along the first direction is between about 1 millimeter and about 25 millimeters.

[0091] In a specific embodiment, the first phase seed wafer is prepared by the following process: In some embodiments of this process, the substrate 101 has a front crystal orientation that is miscut, for example, between 0.2 and 0.8 degrees from (0001) in the m-direction and less than 0.2 degrees in the orthogonal a-direction, and a lattice misorientation of about 5×10 5 cm -2From about 3 × 10 7 cm -2 The intermediate quality substrate includes a substrate that may be a c-plane HVPE substrate having an average dislocation density between about 1×10 and about 1×10. The intermediate quality substrate has the N (back) side patterned and the Ga (front) side masked or covered as described above. An ammonothermal layer having a thickness between about 1 millimeter and about 15 millimeters, or between about 2 millimeters and about 10 millimeters, is preferably a substrate having an average dislocation density between about 1×10 and about 1×10. 19 cm -3 From about 6 × 10 19 cm -3The crystal is grown in the [000-1] direction with an initial oxygen concentration between 0.5 mm and 0.6 mm. The effect of oxygen relaxes not only the macroscopic strains of the HVPE substrate, but also the mismatches caused by local strain centers and lattice mismatches, allowing the crystal to be thickened without producing a rough growth surface as shown diagrammatically in FIG. 12. One or more slices can be prepared from the ammonothermal layer by multi-wire saw cutting with a pitch of between about 0.5 mm and about 2 mm, or between about 0.6 mm and about 1.5 mm. In certain embodiments, after additional optional preparation steps (e.g., one or more of grinding, polishing, chemical mechanical polishing, or final cleaning, etc.), the slices can be used for device fabrication if specifications permit. In certain embodiments, one or more of grinding, polishing, or chemical mechanical polishing processes may be performed in addition to or instead of the multi-wire saw cutting process. In certain embodiments, the quality of the crystal can be further improved by repeating a similar procedure using these slices as seed wafers for the first phase. Phase 1 seed wafers can then be prepared from the slices by etching in phosphoric acid at a temperature between about 100° C. and about 300° C. for about 30 seconds to about 3 hours, or alternatively, by etching in aqueous potassium hydroxide at a temperature between about 60° C. and about 120° C. for about 30 minutes to about 5 hours. In a preferred embodiment, the slices containing the original intermediate quality substrate are recovered and reused as intermediate quality substrates for the growth of additional phase 1 seed wafers after preparing the N-face surface by etching.Finally, if the as-grown (000-1) face of the ammonothermal layer is found to be substantially flat and smooth after growth, i.e., at least 95% of the area of ​​the as-grown (000-1) face has a root-mean-square surface roughness in the first region (e.g., portion 1271 of FIG. 12) between about 0.1 nanometers and about 20 micrometers, or between about 0.1 micrometers and about 5 micrometers, relative to the remainder of the as-grown (000-1) face (e.g., portion 1271 of FIG. 12), and at least 90% of the area of ​​the as-grown (000-1) face does not have recesses with a depth greater than about 5 micrometers and less than about 100 micrometers, or greater than about 20 micrometers and less than 100 micrometers, the crystals can be considered to be second phase crystals. In certain embodiments, some cracks may be present in the second phase crystals.

[0092] Second phase seed crystals can be obtained from the ammonothermal layer portion of the second phase crystals and regrown in the same procedure without a patterned mask. However, it has been found that crystals grown using second phase seeds have significantly improved growth yields even when the initial oxygen concentration is not increased to the same level. For example, in one particular embodiment, the initial oxygen concentration is about 1×10 19 cm -3 From about 6 × 10 19 cm -3 The initial concentration is between about 3 x 10 18 cm -3 From about 1×10 19 cm -3In addition, production efficiency is improved since there is no need to avoid regions with a high initial oxygen content. If the (000-1) face of the as-grown ammonothermal layer is found to be substantially flat and smooth after growth, i.e., 100% of the area of ​​the (000-1) face has a root-mean-square surface roughness between about 0.1 nanometers and about 20 micrometers in the first region (e.g., portion 1271 of FIG. 12) relative to the rest of the (000-1) face (e.g., portion 1271 of FIG. 12), and 100% of the area of ​​the (000-1) face is free of cracks and free of recesses having a depth greater than about 5 micrometers and less than about 100 micrometers, or greater than about 20 micrometers and less than about 100 micrometers, then the crystals can be considered to be of the third phase.

[0093] Third phase seed crystals can be obtained from the ammonothermal layer portion of the third phase crystals and can be regrown in the same procedure without a patterned mask. It has been found that crystals grown using third phase seeds have a much higher growth yield even when the initial oxygen concentration is not increased to the same level. For example, in one particular embodiment, the initial oxygen concentration is about 1×10 19 cm -3 From about 6 × 10 19 cm -3 The initial concentration is between about 3 x 10 18 cm -3 From about 1×10 19 cm -3 In addition, by not having to avoid these regions of high initial oxygen content, the production yield, i.e., the percentage of crystals that can be processed into salable wafers, can also be increased.

[0094] The above sequence of steps provides a method according to one embodiment of the present disclosure. Other alternatives may be provided in which steps are added, one or more steps are removed, or one or more steps are provided in a different order, without departing from the scope of the claims herein. EXAMPLES

[0095] The embodiments provided by the present disclosure are further illustrated by reference to the following examples, which will be apparent to those skilled in the art, many modifications, both to materials and methods, can be practiced without departing from the scope of the present disclosure.

[0096] Example 1 A set of c-plane oriented bulk GaN substrates (some unpatterned, some patterned, some patterned and trenched) were placed in a silver capsule with a baffle with an open area of ​​7% and polycrystalline GaN nutrient. Based on measurements of similar preparation parts by instrumental gas analysis (IGA), the weight ratio of the weight of silver to the weight of polycrystalline GaN nutrient was about 1.76, and the silver had an average oxygen content of about 10 ppm. Prior to being placed in the capsule, polycrystalline GaN was deposited as a film several millimeters thick on Mo foil by reaction of GaCl, formed by bubbling Cl2 into Ga at a temperature of about 825°C, with NH3 at a temperature of about 900°C, and then recovered. The polycrystalline GaN nutrient had a porosity of about 0.66% as measured by mercury intrusion porosimetry, and an oxygen content of about 7 ppm as measured by glow discharge mass spectrometry. Prior to being inserted into the capsule, the polycrystalline GaN nutrient was washed with mineral acid, washed with deionized water, and baked overnight at a temperature of about 60°C. After the insertion of the solid source material, the capsule was evacuated, backfilled with argon, evacuated again, heated to a temperature of about 175°C, backfilled with argon, evacuated again, held at that temperature for about 4.8 hours, and then cooled. The capsule was cooled to dry ice temperature, and HF and then NH3 were added in the gas phase to form NH4F as a mineralizer. The ratios of GaN source and NHF mineralizer to ammonia were about 3.23 and 0.125 by weight, respectively. The capsule was placed in an internally heated high pressure apparatus and heated to about 669°C in the upper source zone and about 679°C in the lower crystal growth zone, and maintained at these temperatures for about 1220 hours, after which it was cooled and removed. As shown in FIG. 8, a wedge-shaped analytical sample was prepared from an ammonothermal GaN layer grown on an unpatterned substrate with a wedge angle α=15°, and SIMS measurements were performed at six points along the surface 855. The measured oxygen, hydrogen, and fluorine concentrations as a function of distance d from the regrowth interface on the large-area surface 102 are shown in FIG. 16A. The maximum oxygen concentration is about 3.6×10 19 cm -3 and the average gradient is approximately -1.8 × 10 in the [0 0 0 -1] direction, measured at depths between 0.6 mm and 2.1 mm from the (0 0 0 -1) seed interface. 20 cm -4The average H / O ratio was about 0.55. The average F / O ratio was about 0.32%. Two parallel slices of the wedge-shaped sample were made perpendicular to surface 855 (i.e., in the plane of the page of FIG. 8) and the two surfaces were ground and chemically mechanically polished. The optical absorption coefficient at a wavelength of 450 nm and the oxygen concentration as a function of depth within the growth region were measured. The results of the optical absorption coefficient (right axis) and oxygen concentration (left axis) are shown in FIG. 16B. The optical absorption coefficient at 450 nm as a function of oxygen concentration is included in FIG. 11.

[0097] Example 2 A set of c-plane oriented bulk GaN substrates (some unpatterned, some patterned, some patterned and trenched) were placed in a silver capsule with a baffle with an open area of ​​15 percent and polycrystalline GaN nutrient. Based on measurements of similar preparation parts by instrumental gas analysis (IGA), the weight ratio of silver to polycrystalline GaN was about 3.11, and the silver had an average oxygen content of about 6 ppm. Prior to encapsulation, polycrystalline GaN was deposited as a film several millimeters thick on Mo foil by reaction of GaCl, formed by bubbling Cl2 into Ga at a temperature of about 825°C, with NH3 at a temperature of about 900°C, as described in U.S. Pat. No. 10,619,239. The polycrystalline GaN nutrient had a porosity of about 0.66% as measured by mercury intrusion porosimetry, and an oxygen content of about 7 ppm as measured by glow discharge mass spectrometry. Prior to insertion into the capsule, the polycrystalline GaN nutrient was washed with mineral acid, rinsed with deionized water, and baked overnight at a temperature of about 120°C. After insertion of the solid raw material, the capsule was evacuated, heated to a temperature of about 200°C, backfilled with argon, reevacuated, refilled, and purged with a continuous flow of argon for about 71 hours as described in U.S. Pat. No. 8,021,481, and reevacuated and held at that temperature for about 92 hours, after which it was cooled, with additional pump / purge cycles during cooling. The capsule was cooled to dry ice temperature, and HF and then NH3 were added in the gas phase to form NHF as the mineralizer. The ratios of GaN raw material and NHF mineralizer to ammonia were about 2.59 and 0.122, respectively, by weight. The capsule was placed in an internally heated high pressure apparatus and heated to about 664°C in the upper source zone and about 681°C in the lower crystal growth zone, maintained at these temperatures for about 960 hours, and then cooled and removed. As shown in FIG. 8, a wedge-shaped analytical sample was prepared from an ammonothermal GaN layer grown on an unpatterned substrate with a wedge angle α=10°, and SIMS measurements were performed at 12 points along the surface 855. The measured oxygen, hydrogen, and fluorine concentrations as a function of distance d from the regrowth interface on the large-area surface 102 are shown in FIG. 17A. The maximum oxygen concentration was about 1.1×10 19 cm-3 The average oxygen gradient from the (0 0 0 -1) seed interface to a maximum depth of about 0.6 mm was about -1.6 × 10 20 cm -4 The average oxygen gradient at a depth between about 0.7 mm and about 1.8 mm from the seed interface was about −1.8×10 in the [0 0 0 −1] direction. 19 cm -4 The average H / O ratio was about 0.61. The average F / O ratio was about 0.55 percent. Two parallel slices of the wedge-shaped specimen were made perpendicular to surface 855 (i.e., in the plane of the page of FIG. 8) and the two surfaces were ground and chemically mechanically polished. The optical absorption coefficient at a wavelength of 450 nm and the oxygen concentration as a function of depth within the growth region were measured. The optical absorption coefficient results (right axis) and oxygen concentration (left axis) are shown in FIG. 17B. The optical absorption coefficient as a function of oxygen concentration is included in FIG. 11.

[0098] Example 3 A set of c-plane oriented bulk GaN substrates (some unpatterned, some patterned, some patterned and trenched) were placed in a silver capsule with a baffle with an open area of ​​15 percent and polycrystalline GaN nutrient. Based on measurements of similar preparation parts by instrumental gas analysis (IGA), the weight ratio of silver to polycrystalline GaN was about 3.59, and the silver had an average oxygen content of about 6 ppm. Prior to encapsulation, polycrystalline GaN was deposited as a film several millimeters thick on Mo foil by reaction of GaCl, formed by bubbling Cl2 into Ga at a temperature of about 825°C, with NH3 at a temperature of about 900°C, as described in U.S. Pat. No. 10,619,239. The polycrystalline GaN nutrient had a porosity of about 0.66% as measured by mercury intrusion porosimetry, and an oxygen content of about 7 ppm as measured by glow discharge mass spectrometry. Prior to insertion into the capsule, the polycrystalline GaN nutrient was washed with mineral acid, rinsed with deionized water, and baked overnight at a temperature of about 120°C. After insertion of the solid feedstock, the capsule was evacuated, heated to a temperature of about 200°C, backfilled with argon, and evacuated again three times for about 42 hours, then cooled, with additional pump / purge cycles during cooling. The capsule was cooled to dry ice temperature, and HF and then NH3 were added in the gas phase to form NHF as the mineralizer. The ratios of GaN feedstock and NHF mineralizer to ammonia were about 2.19 and 0.135, by weight, respectively. The capsule was placed in an internally heated high pressure apparatus and heated to about 664°C in the upper feedstock zone and about 681°C in the lower crystal growth zone, maintained at these temperatures for about 333 hours, then cooled and removed. As shown in Figure 8, a wedge-shaped analytical sample was prepared from an ammonothermal GaN layer grown on an unpatterned substrate with a wedge angle α = 5°, and SIMS measurements were performed at seven points along the surface 855. The measured oxygen, hydrogen, and fluorine concentrations as a function of distance d from the regrowth interface on the large-area surface 102 are shown in Figure 18. The maximum oxygen concentration was about 6.1 x 10 18 cm -3 The average oxygen gradient from the (0 0 0 -1) seed interface to a maximum depth of about 0.75 mm was about -1.65 × 1019 cm -4 The average H / O ratio was about 0.72. The average F / O ratio was about 0.10%. In this case, the fluorine concentration was 5 × 10 15 cm -3 This is only slightly above 20%, which may result in significant uncertainty.

[0099] Example 4 A set of c-plane oriented bulk GaN substrates (some unpatterned, some patterned, some patterned and trenched) were placed in a silver capsule with a baffle with an open area of ​​15 percent and polycrystalline GaN nutrient. Based on measurements of similar preparation parts by instrumental gas analysis (IGA), the weight ratio of silver to polycrystalline GaN was about 1.54, and the silver had an average oxygen content of about 6 ppm. Prior to encapsulation, polycrystalline GaN was deposited as a film several millimeters thick on Mo foil by reaction of GaCl, formed by bubbling Cl2 into Ga at a temperature of about 825°C, with NH3 at a temperature of about 900°C. The polycrystalline GaN nutrient had a porosity of about 0.66% as measured by mercury intrusion porosimetry, and an oxygen content of about 7 ppm as measured by glow discharge mass spectrometry. Prior to insertion into the capsule, the polycrystalline GaN nutrient was washed with mineral acid, rinsed with deionized water, and baked overnight at a temperature of about 120°C. After insertion of the solid source material, the capsule was evacuated, backfilled with argon, evacuated again, heated to a temperature of about 250° C. and held at that temperature under vacuum for about 48 hours, then cooled, and additional pump / purge cycles were performed after cooling. The capsule was cooled to dry ice temperature, and HF and then NH3 were added in the gas phase to form NHF as a mineralizer. The ratios of GaN source and NHF mineralizer to ammonia were about 3.82 and 0.121 by weight, respectively. The capsule was placed in an internally heated high pressure apparatus and heated to about 666° C. in the upper source zone and about 675° C. in the lower crystal growth zone, and maintained at these temperatures for about 936 hours, after which it was cooled and removed. As shown in FIG. 8, a wedge-shaped analytical sample was prepared from an ammonothermal GaN layer grown on an unpatterned substrate with a wedge angle α=80°, and SIMS measurements were performed at five points along the surface 855. The measured oxygen, hydrogen, and fluorine concentrations as a function of distance d from the regrowth interface on the large area surface 102 are shown in Figure 20. The maximum oxygen concentration is approximately 1.9 x 10 18 cm -3 The average oxygen gradient from the (0 0 0 -1) seed interface to a maximum depth of about 3.9 mm was about -4.7 × 10 18 cm-4 The average H / O ratio was about 2.7. The average F / O ratio was about 5 percent.

[0100]

[0001] An embodiment of the present disclosure may provide a method of forming a seed wafer, the method comprising: depositing a patterned mask on a backside (000-1) surface of a c-plane freestanding gallium nitride wafer to form a patterned seed wafer, wherein a front side of the c-plane freestanding gallium nitride wafer has a crystallographic orientation miscut between 0.2 and 0.8 degrees from (0001) in the m-direction and less than 0.2 degrees in the orthogonal a-direction and a crystallographic orientation miscut between about 5×10 5 cm -2 From about 3 × 10 7 cm -2 having a thickness between about 1 millimeter and about 15 millimeters and an average dislocation density between 1×10 19 cm -3 From about 6 × 10 19 cm -3 and an initial oxygen concentration between about 100 and about 150 nm; preparing at least one first ammonothermal seed wafer from the first GaN layer by performing at least one of a wire saw cutting and grinding process; depositing a patterned mask on the (000-1) side of a c-plane freestanding gallium nitride wafer to form a patterned ammonothermal seed wafer; 19 cm -3 From about 6 × 10 19 cm -3and preparing at least one second ammonothermal seed wafer from the second GaN layer by performing at least one of a wire saw cutting and grinding process. The method may further include removing a portion of the first ammonothermal seed wafer by an etching process before depositing the patterned mask on the (000-1) face. The method may further include growing a third GaN layer by an ammonothermal process on the unpatterned open (000-1) face of the second ammonothermal seed wafer in the [000-1] direction, the third GaN layer being grown by an ammonothermal process in the [000-1] direction to a thickness between about 1 millimeter and about 15 millimeters and a thickness of 1×10 19 cm -3 From about 6 × 10 19 cm -3 and the as-grown surface of the third GaN layer is substantially flat with a root mean square roughness between about 1 micrometer and about 100 micrometers. The method may further include preparing at least one third ammonothermal seed wafer from the third GaN layer by performing at least one of a wire saw cutting and grinding process. The claimed method may further include growing a fourth GaN layer by an ammonothermal process on the unpatterned open (000-1) surface of the third ammonothermal seed wafer in a [000-1] direction, the fourth GaN layer having a thickness between about 1 millimeter and about 15 millimeters and a surface roughness of 3×10 18 cm -3 From about 1×10 19 cm -3and wherein at least 95% of the area of ​​the as-grown surface of the fourth GaN layer is substantially flat and smooth, at least 95% of the area of ​​the as-grown (000-1) surface has a root-mean-square roughness, relative to the remainder of the (000-1) surface, of between about 1 micrometer and about 100 micrometers, and at least 90% of the area of ​​the as-grown (000-1) surface does not have recesses with a depth greater than about 20 micrometers.

[0101] While the foregoing is directed to embodiments of the present disclosure, other and further embodiments of the disclosure may be devised without departing from the basic scope thereof, the scope of which is determined by the claims that follow. [Explanation of symbols]

[0102] 101 Substrate 102 large area surface 111 Patterned mask layer 112 Opening 115 Trench 120 Growth-centered 213 Group III metal nitride layer 214 Threading dislocations 215,415 Window Area 217,417 Wing Area 219 Combined Front 221 Group III Metal Nitride Materials 223 Threading dislocation 225 Void 413 Group III Metal Nitrides Boules 419 Array 421 Front 423 Back 431 Free-Standing Ammonothermal Group III Metal Nitride Wafers 502 patterns 631,731 n drift layer 633 n-type or n+ layer 635,735 p-type layer 637 p-type contact 639 n-type contact 730 n+ contact layer 732 Aperture 736 2D Electron Gas Layer 737 Source Contact 740 Laser Ridge or Stripe Structure 841 First Surface 843 Second Surface 845 First Crosscut 847 Second Crosscut 855 Cross-cut surface 859 Reference plane 959 Combined surface 961 Sector Boundary 963 Gap 965 -c Sector Materials 967 A Sector Materials 969 Combined Distance

Claims

1. A crystal having a wurtzite crystal structure, the crystal having a first surface and a second surface opposite the first surface, the crystal containing a Group III metal and nitrogen, As a result of measuring the first surface in a depth direction on the second surface side by a secondary ion mass spectrometer, A crystal, wherein an oxygen concentration has a concentration gradient between said first surface and said second surface, said concentration gradient being between 5×10 16 cm −4 and 1×10 21 cm −4 in a [0 0 0 1] direction.

2. The crystal described in claim 1, wherein the first surface has a maximum dimension greater than 5 millimeters in a first direction and a maximum dimension greater than 15 millimeters in a second direction perpendicular to the first direction.

3. The crystal of claim 2, wherein the first surface has a crystallographic orientation within 30 degrees of {1 0 -1 0}, the first direction including a projection of [0 0 0 1] on the first surface, and an average concentration of stacking faults on the first surface less than 10 3 cm -1 .

4. A crystal as described in claim 1 or 2, wherein the separation distance between the first surface and the second surface is between 100 micrometers and 2000 micrometers.

5. The crystal described in claim 1, wherein, as measured by a secondary ion mass spectrometer in the depth direction of the first surface on the second surface side, the ratio of the hydrogen concentration between the first surface and the second surface to the oxygen concentration is between 0.3 and 10.

6. The crystal of claim 1, wherein the oxygen concentration on at least one of the first surface and the second surface has a local maximum value between 1x10 18 cm -3 and 5x10 19 cm -3 and on at least one of the first surface and the second surface has a local minimum value between 5x10 17 cm -3 and 1x10 19 cm -3 .

7. The crystal of claim 2, characterized by an optical absorption coefficient at a wavelength of 450 nanometers having a local minimum between 0.1 cm -1 and 5 cm -1 at a first location along said first surface and a local maximum between 0.5 cm -1 and 25 cm -1 at a second location along said first direction, said second location being separated from said first location by a distance between 1 millimeter and 25 millimeters.

8. The crystal of claim 7, characterized by an optical absorption coefficient at a wavelength of 450 nanometers having a local minimum between 0.1 cm -1 and 5 cm -1 at a third location along the first surface and a local maximum between 0.5 cm -1 and 25 cm -1 at a fourth location along the first direction, wherein the third location is separated from the second location by a distance between 1 millimeter and 25 millimeters, and the fourth location is separated from the third location by a distance between 1 millimeter and 25 millimeters.

9. The crystal of claim 1, wherein the crystal orientation of the first surface is within 5 degrees of an orientation selected from {1 0 -1 0}, {6 0 -6 ±1}, {4 0 -4 ±1}, {3 0 -3 ±1}, {2 0 -2 ±1}, {3 0 -3 ±2}, {5 0 -5 ±4}, and {1 0 -1 ±1}.

10. The crystal of claim 2, wherein the difference between the maximum value of the {20-21} lattice spacing and the minimum value of the {20-21} lattice spacing at said first surface along said first direction is at least 2×10-5 Å and not more than 3×10-4 Å, and the separation between the local maximum {20-21} lattice constant and the local minimum {20-21} lattice constant along said first direction is between 1 millimeter and 25 millimeters.

11. The method of claim 1, wherein the first surface has a maximum dimension greater than 40 millimeters in the first direction and a crystal orientation within 10 degrees of (0 0 0 1); 3. The crystal of claim 2, wherein a first average oxygen concentration measured in at least four regions on the first surface at a depth of 2 micrometers to 10 micrometers from the first surface as quantified by secondary ion mass spectrometry is between 1×10 16 cm −3 and 5×10 19 cm −3 .

12. The crystal described in claim 11, wherein the first average oxygen concentration is 1.1 to 10 times greater than a second average oxygen concentration quantified by secondary ion mass spectrometry at a depth of 2 to 10 micrometers from the second surface measured in at least four regions on the second surface.

13. The crystal of claim 1, wherein the first surface is characterized in that the impurity concentration of H is greater than 10 17 cm -3 and the impurity concentration of at least one of Li, Na, K, F, Cl, Br, and I is greater than 10 15 cm -3 as measured by quantification using secondary ion mass spectrometry.

14. The first surface, Oxygen (O) between 1×10 16 cm −3 and 5×10 19 cm −3 , Hydrogen (H) between 1×10 16 cm −3 and 8×10 19 cm −3 , and 14. The crystal of claim 13, characterized by an average impurity concentration of at least one of fluorine (F) and chlorine (Cl) between 1×10 15 cm −3 and 1×10 19 cm −3 .

15. The first surface, Oxygen (O) between 1×10 16 cm −3 and 5×10 19 cm −3 , Hydrogen (H) between 1×10 16 cm −3 and 8×10 19 cm −3 , and 14. The crystal of claim 13, characterized by an impurity concentration of at least one of sodium (Na) and potassium (K) between 3×10 15 cm −3 and 1×10 18 cm −3 .

16. The crystal described in claim 13, wherein the ratio of the impurity concentration of fluorine to the oxygen concentration is between 0.05% and 10%.

17. The crystal described in claim 13, wherein the first surface and the second surface are substantially free of implantation damage or plasma damage to a depth of 10 micrometers.

18. A method for producing a GaN crystal comprising: preparing a seed crystal containing a group III metal and nitrogen in a sealable container; a first polycrystalline GaN nutrient material; an oxygen source; and a mineralizer; A method for producing a crystal, comprising: a growth step in which, after the preparation step, a relative oxygen concentration in the container is changed over time by heating the container to increase the temperature therein, adding ammonia to the container, and pressurizing the container, thereby growing a GaN layer on the seed crystal.

19. A method for producing a crystal as described in claim 18, wherein in the preparation step, the oxygen source is selected from at least one of the following: residual moisture in the first polycrystalline GaN nutrient material, Ga2O3 in or on one or more surfaces of the first polycrystalline GaN nutrient material, a second polycrystalline GaN nutrient material having a particle size smaller than that of the first polycrystalline GaN, water, and Ga2O3 in the form of powder, grit, or polycrystalline ceramic.

20. The method for producing a crystal as described in claim 18, further comprising an additional preparation step of controlling the temperature of the first polycrystalline GaN nutrient material placed in the container to a temperature between 50°C and 600°C prior to the addition of ammonia to the container during the growth step.

21. The method for producing a crystal as described in claim 18, wherein the growing step includes controlling the temperature of the first polycrystalline GaN nutrient material disposed in the internal volume in an oxidizing acid at a temperature between 25°C and 200°C, or in O2 or air at a temperature between 300°C and 1000°C.

22. The method of claim 21, further comprising the additional step of placing oxygen-containing silver metal in the container; The method for producing a crystal according to claim 18 , wherein the growing step further comprises the step of heating the silver metal.